A potential new sea surface temperature proxy based on isomeric highly branched isoprenoid lipid biomarkers: EZ25 - Belt, Simon T.; Smik, Lukas; Husum, Katrine; Knies, Jochen (Organic Geochemistry, 2025)
Two tri-unsaturated and isomeric (E/Z) highly branched isoprenoid (HBI) diatom lipid biomarkers were quantified in 228 water column samples collected from the English Channel, West Svalbard (Arctic), the Scotia Sea (Southern Ocean) and East Antarctica. We found that the relative amounts of the two HBIs correlate well with water temperatures taken at the time of sampling. Based on these findings and some other HBI data reported previously, we suggest that the proportion of the HBI E-isomer (termed EZ25) may serve as a new proxy for palaeo sea surface temperatures, including in the polar regions. Next steps will involve determination of EZ25 in surface and downcore sediments to ascertain whether the temperature response described herein translates well to the geological record.
Keywords: Scotiahavet; Sørishavet; biogeokjemi; biomarkører; geologi; paleontologi; polarområdene

Abundance and Diversity of Aerobic Anoxygenic Phototrophic Bacteria in Polar Plant Microbiomes - Mäkinen, Emilia A.; Franz, Ole; Ihalainen, Janne A.; Helander, Marjo; Nissinen, Riitta; Mathew, Suni A.; Saloniemi, Irma; Saikkonen, Kari (Physiologia Plantarum, 2025)
ABSTRACT Here, we examined the occurrence of plant-associated aerobic anoxygenic phototrophic bacteria (AAPB) across polar regions. Recently found in polar soils and cold-climate plants, AAPBs are photoheterotrophs that rely on environmental organic carbon but capture solar energy via anoxygenic photosynthesis. We revealed the abundance of AAPBs by extracting bacteria from plant tissues and imaging the colonies with bacteriochlorophyll-based near-infrared fluorescence. The taxonomic distribution of AAPBs was determined via 16S rRNA gene analysis. From the northern hemisphere, we describe AAPBs from the leaf endo- and phyllospheres of numerous sub- and Arctic plant species in Northern Finland, Svalbard, and Greenland. In the southern hemisphere, we focused on AAPBs in the root and leaf endospheres and the phyllospheres of Deschampsia antarctica in Chilean Patagonia and maritime Antarctica. Additionally, we describe AAPB from the tissues of several other plant species in Patagonia. We found AAPBs commonly associated with the sampled plant species across both hemispheres. A diversity of Alphaproteobacteria was found to contain the AAP capability: at all sampling sites, Sphingomonas was the most abundant taxon (up to 60%), while Methylobacteria made up a notable proportion of sub-Arctic and sub-Antarctic AAPB samples (up to 32%). In contrast to previous studies describing Methylobacteria frequently in various plant communities, AAP-containing Methylobacteria were virtually absent from our high-latitude sites. With diverse AAPB taxa found ubiquitously across polar regions and plant tissues, our results call attention to the potential ecological interaction between AAPBs and their plant hosts.
Keywords: Antarktis; biodiversitet; biogeografi; biologi; mikroorganismer; polarområdene

Editorial: Microplastics and nanoplastics in polar areas: Arctic, Antarctica, and the world’s glaciers - Corami, Fabiana; Iannilli, Valentina; Hallanger, Ingeborg G. (Frontiers in Marine Science, 2025)
Plastic particles are present in biotic and abiotic matrices; hence, plastic pollution is a global issue involving terrestrial and marine fauna and poses a threat to humans. Ocean circulation is a crucial vector of microplastics worldwide. Plastic pollution is among the significant threats to the ocean ecosystem. Studies and papers on plastic pollution in the oceans worldwide have been reported. However, the distribution, characterization, and abundance of micro- and nano plastics in the global ocean still need to be carefully investigated. Once plastics are present in the environment, they denature, degrade, and are more prone to fragmentation. It is well established that large plastic objects and macroplastics fragment into mesoplastics and large microplastics through photodegradation and weathering. Hence microplastics easily break up into fragments <100 µm (small microplastics, SMPs) or even into sub-micrometric particles, the nanoplastics. The small size of these SMPs and nanoplastics allows them to be ingested by different organisms according to their mouthparts’ size. Besides, this fragmentation will enable additives and plasticizers to be released into the environment, where they may pose a threat to biota throughout the trophic web in various ecosystems, e.g., from oceans and soils to glaciers. Micro- and nanoplastics (MNPs) can be transported over long distances, together with the other airborne particles. As a result of long-range transport and short-range transport, airborne MNPs can be carried from worldwide to mountain glaciers; from mid-latitudes, they can reach the very high and very low latitudes, i.e., the Arctic and Antarctica. Due to global climate change, warm ocean streams heavily affect the sea circulation in polar areas, carrying regulated and emerging pollutants, microplastics being among them. In this scenario, polar environments may be significantly enriched by MNPs carried by warmer ocean currents intruding into the polar oceans and those in atmospheric aerosol. MNPs may threaten the sea ice formation and enhance the melting of glaciers. The melting and disappearance of glaciers and the intrusion of warm currents into polar areas are also compounded by the thawing of permafrost, which can release pollutants, including MNPs. This Research Topic aims to study the interconnected pathways of MNPs that are paramount to understanding the global microplastic cycle and how climate change alters polar environments and the rest of the world. Furthermore, we aim to identify bioindicators in marine species, populations, and ecosystems, while acknowledging the interconnectedness of freshwater, terrestrial and atmospheric environments to the polar environment. Research on world glaciers will provide a comprehensive evaluation of the impacts of plastic pollution on the marine polar environment and biota, including impacts on humans.
Keywords: Antarktis; forurensning; isbreer; klimaendringer; mikroplast; miljøgifter; polarområdene; økologi; økosystemer

Using a multi-layer snow model for transient paleo-studies: surface mass balance evolution during the Last Interglacial - Hoang, Thi-Khanh-Dieu; Quiquet, Aurélien; Dumas, Christophe; Born, Andreas; Roche, Didier M. (Clim. Past, 2025)
During the Quaternary, ice sheets experienced several retreat–advance cycles, strongly influencing climate patterns. In order to properly simulate these phenomena, it is preferable to use physics-based models instead of parameterizations to estimate the surface mass balance (SMB), which strongly influences the evolution of the ice sheet. To further investigate the potential of these SMB models, this work evaluates the BErgen Snow SImulator (BESSI), a multi-layer snow model with high computational efficiency, as an alternative to providing the SMB for the Earth system model iLOVECLIM for multi-millennial simulations as in paleostudies. We compare the behaviors of BESSI and insolation temperature melt (ITM), an existing SMB scheme of iLOVECLIM during the Last Interglacial (LIG). Firstly, we validate the two SMB models using the regional climate model Mod- èle Atmosphérique Régional (MAR) as forcing and reference for the present-day climate over the Greenland and Antarctic ice sheets. The evolution of the SMB over the LIG (130–116 ka) is computed by forcing BESSI and ITM with transient climate forcing obtained from iLOVECLIM for both ice sheets. For present-day climate conditions, both BESSI and ITM exhibit good performance compared to MAR despite a much simpler model setup. While BESSI performs well for both Antarctica and Greenland for the same set of parame- ters, the ITM parameters need to be adapted specifically for each ice sheet. This suggests that the physics embedded in BESSI allows better capture of SMB changes across varying climate conditions, while ITM displays a much stronger sen- sitivity to its tunable parameters. The findings suggest that BESSI can provide more reliable SMB estimations for the iLOVECLIM framework to improve the model simulations of the ice sheet evolution and interactions with climate for multi-millennial simulations.
Keywords: Antarktis; innlandsis; klimamodeller; paleoklimatologi; polarområdene

Community estimate of global glacier mass changes from 2000 to 2023 - Zemp, Michael; Jakob, Livia; Dussaillant, Inés; Nussbaumer, Samuel U.; Gourmelen, Noel; Dubber, Sophie; A, Geruo; Abdullahi, Sahra; Andreassen, Liss Marie; Berthier, Etienne; Bhattacharya, Atanu; Blazquez, Alejandro; et al. (Nature, 2025)
Glaciers are indicators of ongoing anthropogenic climate change1. Their melting leads to increased local geohazards2, and impacts marine3 and terrestrial4,5 ecosystems, regional freshwater resources6, and both global water and energy cycles7,8. Together with the Greenland and Antarctic ice sheets, glaciers are essential drivers of present9,10 and future11–13 sea-level rise. Previous assessments of global glacier mass changes have been hampered by spatial and temporal limitations and the heterogeneity of existing data series14–16. Here we show in an intercomparison exercise that glaciers worldwide lost 273 ± 16 gigatonnes in mass annually from 2000 to 2023, with an increase of 36 ± 10% from the first (2000–2011) to the second (2012–2023) half of the period. Since 2000, glaciers have lost between 2% and 39% of their ice regionally and about 5% globally. Glacier mass loss is about 18% larger than the loss from the Greenland Ice Sheet and more than twice that from the Antarctic Ice Sheet17. Our results arise from a scientific community effort to collect, homogenize, combine and analyse glacier mass changes from in situ and remote-sensing observations. Although our estimates are in agreement with findings from previous assessments14–16 at a global scale, we found some large regional deviations owing to systematic differences among observation methods. Our results provide a refined baseline for better understanding observational differences and for calibrating model ensembles12,16,18, which will help to narrow projection uncertainty for the twenty-first century11,12,18.
Keywords: Antarktis; fjernmåling; glasiologi; havnivåstigning; hydrologi; isbreer; klimaendringer; kryosfæren; polarområdene

A virtual geobibliography of polar tourism and climate change - Demiroglu, O. Cenk; Bohn, Dorothee; Dannevig, Halvor; Hall, C. Michael; Hehir, Christy; Lundmark, Linda; Nilsson, Robert O.; Olsen, Julia; Tervo-Kankare, Kaarina; Vereda, Marisol; Welling, Johannes (Journal of Sustainable Tourism, 2024)
The polar regions are increasingly at the center of attention as the hot spots of climate crisis as well as tourism development. The recent IPCC reports highlight several climate change risks for the rather carbon-intensive and weather-based/dependent polar tourism industry in the Arctic and the Antarctic. This study presents the scholarly state-of-knowledge on tourism and climate change in the polar regions with a literature survey extending beyond the Anglophone publications. As a supporting tool, we provide a live web GIS application based on the geographical coverages of the publications and filterable by various spatial, thematic and bibliographical attributes. The final list of 137 publications indicates that, regionally, the Arctic has been covered more than the Antarctic, whilst an uneven distribution within the Arctic also exists. In terms of the climate change risks themes, climate risk research, i.e. impact and adaptation studies, strongly outnumbers the carbon risk studies especially in the Arctic context, and, despite a balance between the two main risk themes, climate risk research in the Antarctic proves itself outdated. Accordingly, the review ends with a research agenda based on these spatial and thematic gaps and their detailed breakdowns.
Keywords: Antarktis; bibliografi; geobibliografi; klimaendringer; polarområdene; turisme

Conjugate aurora observations by the Gjøa and Discovery expeditions - Egeland, Alv (Hist. Geo Space. Sci., 2024)
From 1901 to 1912 – known as the “heroic period” of Arctic and Antarctic exploration – great inroads were made (not only geographic but also scientific) to our knowledge of the continent. At Amundsen's Expedition through the Northwest Passage, measurements of the geomagnetic field and visual auroras were carried out for 19 months at Gjoa Haven (Gjøahavn in Norwegian; geographic coordinates 68°37′10′′ N, 95°53′25′′ W). Scott's Discovery Expedition – at Cape Armitage, McMurdo (coordinates 77.86° S, 166.69° E), Antarctica – carried out the same type of measurements. Their observations were carried out geomagnetically conjugate to Gjoa Haven, with both stations close to 78° magnetic latitude. In addition, measurements were overlapping in time during 1903–1904. However, these two stations are located at different longitudes, so there is a difference in local time between the stations of about 6.5 h. Gjoa Haven and Cape Armitage are conveniently located for separating disturbances in the polar cap regions caused by solar electromagnetic radiations or the solar wind. Auroras were observed during 7 months per year. This gave a unique possibility to compare conjugate characteristics of polar cap auroras. Comparing conjugate geophysical data introduces some difficulties. During the winter season at Gjoa Haven, they had a bright summer in Antarctica, and visa versa. Thus, simultaneous temporal and spatial ionospheric variations can be marked differently. Still, the average diurnal and seasonal variations were similar. The quantity of the auroral data from Cape Armitage was larger because there they had a continuous watch of the sky. The main findings regarding polar cap auroras are the following. Three different auroral forms dominate the polar cap. Low-intensity auroral bands – then called streamers – were the dominating auroral forms morning and afternoon. The number of auroral events in 1903 was nearly twice that in 1902 and 1904. A marked midwinter maximum was observed at both stations. Many displays were observed poleward of the oval. The large fraction was associated with weak magnetic disturbances. Some forms of polar cap aurora have special magnetic signatures and seem to be anti-correlated with Kp. They can be mapped even if they are not seen. According to recent satellite measurements (Newell et al., 2009), they are probably caused by polar rain and/or photoelectrons.
Keywords: Antarktis; Discoveryekspedisjonen; fysikk; polarfarere; polarområdene; romfysikk; sørlys

Short- and long-term variability of the Antarctic and Greenland ice sheets - Hanna, Edward; Topál, Dániel; Box, Jason E.; Buzzard, Sammie; Christie, Frazer D. W.; Hvidberg, Christine; Morlighem, Mathieu; De Santis, Laura; Silvano, Alessandro; Colleoni, Florence; Sasgen, Ingo; Banwell, Alison F.; et al. (Nature Reviews Earth & Environment, 2024)
The variability of the Antarctic and Greenland ice sheets occurs on various timescales and is important for projections of sea level rise; however, there are substantial uncertainties concerning future ice-sheet mass changes. In this Review, we explore the degree to which short-term fluctuations and extreme glaciological events reflect the ice sheets’ long-term evolution and response to ongoing climate change. Short-term (decadal or shorter) variations in atmospheric or oceanic conditions can trigger amplifying feedbacks that increase the sensitivity of ice sheets to climate change. For example, variability in ocean-induced and atmosphere-induced melting can trigger ice thinning, retreat and/or collapse of ice shelves, grounding-line retreat, and ice flow acceleration. The Antarctic Ice Sheet is especially prone to increased melting and ice sheet collapse from warm ocean currents, which could be accentuated with increased climate variability. In Greenland both high and low melt anomalies have been observed since 2012, highlighting the influence of increased interannual climate variability on extreme glaciological events and ice sheet evolution. Failing to adequately account for such variability can result in biased projections of multi-decadal ice mass loss. Therefore, future research should aim to improve climate and ocean observations and models, and develop sophisticated ice sheet models that are directly constrained by observational records and can capture ice dynamical changes across various timescales.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer; polarområdene

The Use of Weather, Water, Ice, and Climate (WWIC) Information in the Polar Regions: What Is Known after the Decadelong Polar Prediction Project? - Heinrich, Victoria J.; Stewart, Emma J.; Liggett, Daniela; Carrasco, Jorge F.; Dawson, Jackie; Lamers, Machiel; Ljubicic, Gita J.; Jeuring, Jelmer; Thoman, Rick (Weather, Climate, and Society, 2024)
The polar regions are facing a wide range of compounding challenges, from climate change to increased human activity. Infrastructure, rescue services, and disaster response capabilities are limited in these remote environments. Relevant and usable weather, water, ice, and climate (WWIC) information is vital for safety, activity success, adaptation, and environmental protection. This has been a key focus for the World Meteorological Organization’s (WMO) Polar Prediction Project (PPP), and in particular its “Societal and Economic Research and Applications” (PPP-SERA) Task Team, which together over a decade have sought to understand polar WWIC information use in relation to operational needs, constraints, and decision contexts to inform the development of relevant services. To understand research progress and gaps on WWIC information use during the PPP (2013–23), we undertook a systematic bibliometric review of aligned scholarly peer-reviewed journal articles (n = 43), examining collaborations, topics, methods, and regional differences. Themes to emerge included activity and context, human factors, information needs, situational awareness, experience, local and Indigenous knowledge, and sharing of information. We observed an uneven representation of disciplinary backgrounds, geographic locations, research topics, and sectoral foci. Our review signifies an overall lack of Antarctic WWIC services research and a dominant focus on Arctic sea ice operations and risks. We noted with concern a mismatch between user needs and services provided. Our findings can help to improve WWIC services’ dissemination, communication effectiveness, and actionable knowledge provision for users and guide future research as the critical need for salient weather services across the polar regions remains beyond the PPP. Significance Statement Every day, people in the Arctic and Antarctic use weather, water, ice, and climate information to plan and carry out outdoor activities and operations in a safe way. Despite advances in numerical weather prediction, technology, and product development, barriers to accessing and effectively communicating high-quality usable observations, forecasts, and actionable knowledge remain. Poorer services, prediction accuracy, and interpretation are exacerbated by a lack of integrated social science research on relevant topics and a mismatch between the services provided and user needs. As a result, continued user engagement, research focusing on information use, risk communication, decision-making processes, and the application of science for services remain highly relevant to reducing risks and improving safety for people living, visiting, and working in the polar regions.
Keywords: Antarktis; klimaendringer; klimatologi; meteorologi; polarområdene

Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Regional polar warming linked to poleward moisture transport variability - Bintanja, Richard; Graversen, Rune Grand; Kolbe, Marlen (Environmental Research: Climate, 2023)
Polar warming, ice melt and strong precipitation events are strongly affected by episodic poleward advection of warm and moist air (Woods and Caballero 2016 J. Clim. 29 4473–85; Wille et al 2019 Nat. Geosci. 12 911–6), which, in turn, is linked to variability in poleward moisture transport (PMT) (Nash et al 2018 J. Geophys. Res. Atmos. 123 6804–21). However, processes governing regional impacts of PMT as well as long-term trends remain largely unknown. Here we use an ensemble of state-of-the-art global climate models in standardized scenario simulations (1850–2100) to show that both the Arctic and the Antarctic exhibit distinct geographical patterns of PMT-related warming. Specifically, years with high PMT experience considerable warming over subarctic Eurasia and West-Antarctica (Raphael et al 2016 Bull. Am. Meteorol. Soc. 97 111–21), whereas precipitation is distributed more evenly over the polar regions. The warming patterns indicate preferred routes of atmospheric rivers (Woods and Caballero 2016 J. Clim. 29 4473–85), which may regionally enhance atmospheric moisture content, cloud cover, and downward longwave radiative heating in years with comparatively high PMT (Scott et al 2019 J. Clim. 32 665–84). Trend-analyses reveal that the link between PMT-variability and regional precipitation patterns will weaken in both polar regions. Even though uncertainties associated with intermodel differences are considerable, the advection of warm and moist air associated with PMT-variability is likely to increasingly cause mild conditions in both polar regions, which in the Arctic will reinforce sea-ice melt. Similarly, the results suggest that warm years in West-Antarctica disproportionally contribute to ice sheet melt (Trusel et al 2015 Nat. Geosci. 8 927–32), enhancing the risk of ice-sheet instabilities causing accelerated and sudden sea-level rise.
Keywords: Antarktis; global oppvarming; klimamodeller; meteorologi; polarområdene

Strong and lasting impacts of past global warming on baleen whales and their prey - Cabrera, Andrea A; Schall, Elena; Bérubé, Martine; Anderwald, Pia; Bachmann, Lutz; Berrow, Simon; Best, Peter B; Clapham, Phillip J; Cunha, Haydée A.; Dalla Rosa, Luciano; Dias, Carolina; Findlay, Kenneth P.; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real-time effects into their long-term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long-term responses of natural populations to periods with global warming. The effects of this post-LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large-scale climate fluctuations during the post-LGM affected baleen whales and their prey, we conducted an extensive, large-scale analysis of the long-term effects of the post-LGM warming on abundance and inter-ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome-wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post-LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean-wide expansions and decreases in abundance that were initiated by the post-LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long-lasting impacts of global warming on marine fauna.
Keywords: Sørishavet; klimaendringer; marin biologi; polarområdene

Allometric relationships of ecologically important Antarctic and Arctic zooplankton and fish species - Schaafsma, Fokje L.; David, Carmen L.; Kohlbach, Doreen; Ehrlich, Julia; Castellani, Giulia; Lange, Benjamin A.; Vortkamp, Martina; Meijboom, André; Fortuna-Wünsch, Anna; Immerz, Antonia; Cantzler, Hannelore; Klasmeier, Apasiri; et al. (Polar Biology, 2022)
Allometric relationships between body properties of animals are useful for a wide variety of purposes, such as estimation of biomass, growth, population structure, bioenergetic modelling and carbon flux studies. This study summarizes allometric relationships of zooplankton and nekton species that play major roles in polar marine food webs. Measurements were performed on 639 individuals of 15 species sampled during three expeditions in the Southern Ocean (winter and summer) and 2374 individuals of 14 species sampled during three expeditions in the Arctic Ocean (spring and summer). The information provided by this study fills current knowledge gaps on relationships between length and wet/dry mass of understudied animals, such as various gelatinous zooplankton, and of animals from understudied seasons and maturity stages, for example, for the krill Thysanoessa macrura and larval Euphausia superba caught in winter. Comparisons show that there is intra-specific variation in length–mass relationships of several species depending on season, e.g. for the amphipod Themisto libellula. To investigate the potential use of generalized regression models, comparisons between sexes, maturity stages or age classes were performed and are discussed, such as for the several krill species and T. libellula. Regression model comparisons on age classes of the fish E. antarctica were inconclusive about their general use. Other allometric measurements performed on carapaces, eyes, heads, telsons, tails and otoliths provided models that proved to be useful for estimating length or mass in, e.g. diet studies. In some cases, the suitability of these models may depend on species or developmental stages.
Keywords: Sørishavet; biomasse; dyreplankton; fisker; marin biologi; marin økologi; polarområdene; zooplankton

Spatial and interspecific variation of accumulated highly toxic trace elements between fifteen bird species feathers from Antarctic, Arctic and China - Sun, Yayue; Lu, Zhibo; Xiao, Kaiyan; Zeng, Lingyun; Wang, Juan; Zhang, Yanyun; Gabrielsen, Geir Wing (Environmental Technology & Innovation, 2022)
To assess the impact of human activities and other factors on the levels of highly toxic trace elements in the environment, the contents of eight highly toxic trace elements (arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn)) in feathers of 15 bird species from the Prydz Bay region in the Antarctic, Ny-Alsund region in the Arctic, and eastern China were evaluated in this study. Results showed that feathers collected from the Antarctic showed the highest As, Cu, and Hg contents (1.65–2.85, 9.58–18.56, and 4.77–8.76 μg/g dw, respectively) of the different study areas, whereas Arctic feathers exhibited the highest mean Pb levels (1.82–3.19 μg/g dw), and feathers from China showed significantly lower accumulations of Cr, Ni, Pb, and Zn compared with the other two areas. Overall, most of the studied highly toxic trace element contents in bird feathers from the densely populated and polluted area of eastern China were lower than those from remote polar regions, which are negligibly affected by human activities. In addition, feathers from the Arctic did not show higher highly toxic trace element contents than those of the more remote Antarctic. These results are thus inferred to reflect differences in the dietary structure of birds in the different habitats, as well as historical climate change. Carbon (δ13C) and nitrogen (δ15N) stable isotope ratios of feathers were also measured to evaluate the relationship between diet and highly toxic trace elements. Results showed that highly toxic trace element contents did not increase with increasing trophic levels. Moreover, the methylmercury content accounted for 87.57%–98.59% of the total mercury in all feather samples, regardless of location and species, confirming that most of the mercury entering the feathers is methylated. This finding suggests that the form of mercury changes during the process of transference from internal tissues to feathers, which improves our understanding of the mechanism by which feathers excrete mercury, this behavior greatly reduces the harm to bird health caused by mercury. This study confirms that measuring contaminants in feathers is a long-term and effective method for monitoring highly toxic trace elements pollution in particular environments, making future monitoring of highly toxic trace elements pollution in the polar regions, as well as more typical environments, more convenient.
Keywords: Antarktis; miljøgifter; polarområdene; sjøfugler; økotoksikologi

First discrete iron(II) records from Dome C (Antarctica) and the Holtedahlfonna glacier (Svalbard) - Burgay, François; Barbaro, Elena; Cappelletti, David; Turetta, Clara; Gallet, Jean-Charles; Isaksson, Elisabeth; Stenni, Barbara; Dreossi, Giuliano; Scoto, Federico; Barbante, Carlo; Spolaor, Andrea (Chemosphere, 2021)
Fe(II) is more soluble and bioavailable than Fe(III) species, therefore the investigation of their relative abundance and redox processes is relevant to better assess the supply of bioavailable iron to the ocean and its impact on marine productivity. In this context, we present a discrete chemiluminescence-based method for the determination of Fe(II) in firn matrices. The method was applied on discrete samples from a snow pit collected at Dome C (DC, Antarctica) and on a shallow firn core from the Holtedahlfonna glacier (HDF, Svalbard), providing the first Fe(II) record from both Antarctica and Svalbard. The method showed low detection limits (0.006 ng g−1 for DC and 0.003 ng g−1 for the HDF) and a precision ranging from 3% to 20% RSD. Fe(II) concentrations ranged between the LoD and 0.077 ng g−1 and between the LoD and 0.300 ng g−1 for the Antarctic and Arctic samples, respectively. The Fe(II) contribution with respect to the total dissolved Fe was comparable in both sites accounting, on average, for 5% and 3%, respectively. We found that Fe(II) correctly identified the Pinatubo/Cerro Hudson eruption in the DC record, demonstrating its reliability as volcanic tracer, while, on the HDF core, we provided the first preliminary insight on the processes that might influence Fe speciation in firn matrices (i.e. organic ligands and pH influences).
Keywords: Antarktis; glasiologi; kjemi; polarområdene

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Cancellation of the Precessional Cycle in δ18O Records During the Early Pleistocene - Morée, Anne L; Sun, Tianyi; Bretones, Anaïs; Straume, Eivind O; Nisancioglu, Kerim; Gebbie, Geoffrey (Geophysical Research Letters, 2021)
The dominant pacing of glacial-interglacial cycles in deep-ocean δ18O records changed substantially during the Mid-Pleistocene Transition. The precessional cycle (∼23 ky) is absent during the Early Pleistocene, which we show can be explained by cancellation of the hemispherically antiphased precessional cycle in the Early Pleistocene interior ocean. Such cancellation develops due to mixing of North Atlantic and Southern Ocean δ18O signals at depth, and shows characteristic spatial patterns. We explore the cancellation potential for different North Atlantic and Southern Ocean deep-water source δ18O values using a tracer transport ocean model. Cancellation of precession occurs for all signal strengths and is widespread for a signal strength typical for the Early Pleistocene. Early Pleistocene precessional power is therefore likely incompletely archived in deep-sea δ18O records, concealing the true periodicity of the glacial cycles in the two hemispheres.
Keywords: Sørishavet; geofysikk; innlandsis; oseanografi; paleontologi; polarområdene

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Hvordan vet vi det vi vet om global oppvarming? - Seip, Knut Lehre (Naturen, 2021)
Hvordan vet vi det vi vet om global oppvarming? Denne artikkelen diskuterer grunnlaget for det vi vet med stor sikkerhet. I artikkelen diskuterer vi 12 temaer, og velger ut én eller to metoder som illustrerer hvordan kunnskap er skaffet til veie for hvert av temaene.
Keywords: Antarktis; global oppvarming; klimaendringer; klimatologi; polarområdene

Satellite and ground based estimates for ice surface velocities in the part of central Dronning Maud Land, East Antarctica: Implications for ice flux calculations - Thakur, Praveen K; Swain, Ashit K; Dhote, Pankaj R; Kumar, Pradeep; Kaushik, Suvrat; Gajbhiye, Deepak; Mahagaonkar, Anirudha; Sharma, Vishal; Dharwadkar, Amit; Aggarwal, S P; Beg, Javed; Chauhan, Prakash; et al. (Polar Science, 2021)
The ice sheet and glaciers of Antarctica and Greenland represent the largest sources of freshwater on planet Earth. The understanding and quantification of their dynamic properties such as albedo, precipitation, ice mass movement, and ice elevation changes are critical for the improved climate and mass balance models. The present study utilizes space-borne optical and synthetic aperture radar (SAR) imagery to measure the ice surface velocity at high spatial resolution for a part of the central Dronning Maud Land (cDML), East Antarctica. The datasets from Landsat-8 and Sentinel-1 SAR satellite are used for ice stream velocity estimation using feature-offset tracking and differential interferometric SAR (DInSAR) methods. The derived velocity products are validated with ground based stakes network at annual time scale. The fundamental ice flow laws are used to estimate the ice outflux or discharge for selected ice stream drainage basins of cDML at fluxgate locations. The ice stream basin has been delineated using combination of elevation, slope and continental scale velocity maps. The ice influx for study area is estimated using ECMWF fifth generation reanalysis (ERA5) and Regional Atmospheric Climate Model (RACMO) v2.3 model outputs. The estimated influx and outflux are in the ranges of 0.18–4.167 Gt/y and 0.201 to 1.278 Gt/y respectively, indicating net positive mass balance for the selected area.
Keywords: Dronning Maud Land; glasiologi; innlandsis; polarområdene

Full-Depth Global Estimates of Ocean Mesoscale Eddy Mixing From Observations and Theory - Groeskamp, Sjoerd; LaCasce, Joseph H; McDougall, Trevor J; Rogé, Marine (Geophysical Research Letters, 2020)
Mixing by mesoscale eddies profoundly impacts climate and ecosystems by redistributing and storing dissolved tracers such as heat and carbon. Eddy mixing is parameterized in most numerical models of the ocean and climate. To reduce known sensitivity to such parameterizations, observational estimates of mixing are needed. However, logistical and technological limitations obstruct our ability to measure global time-varying mixing rates. Here, we extend mixing length theory with mean-flow suppression theory, and first surface modes, to estimate mixing from readily available observational-based climatological data, of salinity, temperature, pressure, and eddy kinetic energy at the sea surface. The resulting full-depth global maps of eddy mixing can reproduce the few available direct estimates and confirm the importance of mean-flow suppression of mixing. The results also emphasize the significant effect of eddy surface intensification and its relation to the vertical density stratification. These new insights in mixing dynamics will improve future mesoscale eddy mixing parameterizations.
Keywords: Sørishavet; geovitenskap; havet; klimatologi; polarområdene; vannvirvler; økosystemer

Supercooled Southern Ocean Waters - Haumann, F Alexander; Moorman, Ruth; Riser, Stephen C; Smedsrud, Lars H; Maksym, Ted; Wong, Annie P S; Wilson, Earle A; Drucker, Robert; Talley, Lynne D; Johnson, Kenneth S; Key, Robert M; Sarmiento, Jorge L (Geophysical Research Letters, 2020)
In cold polar waters, temperatures sometimes drop below the freezing point, a process referred to as supercooling. However, observational challenges in polar regions limit our understanding of the spatial and temporal extent of this phenomenon. We here provide observational evidence that supercooled waters are much more widespread in the seasonally ice-covered Southern Ocean than previously reported. In 5.8% of all analyzed hydrographic profiles south of 55°S, we find temperatures below the surface freezing point (“potential” supercooling), and half of these have temperatures below the local freezing point (“in situ” supercooling). Their occurrence doubles when neglecting measurement uncertainties. We attribute deep coastal-ocean supercooling to melting of Antarctic ice shelves and surface-induced supercooling in the seasonal sea-ice region to wintertime sea-ice formation. The latter supercooling type can extend down to the permanent pycnocline due to convective sinking plumes—an important mechanism for vertical tracer transport and water-mass structure in the polar ocean.
Keywords: Sørishavet; havis; hydrografi; isbrem; isshelf; oseanografi; polarområdene; sjøis; superkjøling

Interhemispheric Asymmetry of Large-Scale Electron Density Gradients in the Polar Cap Ionosphere: UT and Seasonal Variations - Jin, Yaqi; Xiong, Chao (Journal of Geophysical Research: Space Physics, 2020)
The high-latitude ionosphere is highly dynamical with significant irregularities and density gradients. However, the spatial and temporal distributions of density gradients and irregularities are very different between the Arctic and Antarctic. In this report, we study the interhemispheric asymmetry of the large-scale (100 km) density gradients in both polar caps. Our results show that density gradients in the Arctic are enhanced during local winter (December solstice) with a peak around 19 UT. The UT and spatial distributions in the Antarctic local winter (June solstice) are similar to the Arctic except that they are reversed by 12 hr, which indicates a mirror symmetry between hemispheres. The 12-hr difference in the peak density gradients can be explained by the displacements between the geographic and geomagnetic poles. The only asymmetry (anomaly) is the persistence of strong density gradients in the southern polar cap during local summer (December solstice).
Keywords: Antarktis; fysikk; geovitenskap; ionosfæren; polarområdene

CloudSat-Inferred Vertical Structure of Snowfall Over the Antarctic Continent - Lemonnier, Florentin; Madeleine, Jean-Baptiste; Claud, Chantal; Palerme, Cyril; Genthon, Christophe; L'Ecuyer, Tristan; Wood, Norman B (Journal of Geophysical Research: Atmospheres, 2020)
Current global warming is causing significant changes in snowfall in polar regions, directly impacting the mass balance of the ice caps. The only water supply in Antarctica, precipitation, is poorly estimated from surface measurements. The onboard cloud-profiling radar of the CloudSat satellite provided the first real opportunity to estimate solid precipitation at continental scale. Based on CloudSat observations, we propose to explore the vertical structure of precipitation in Antarctica over the 2007–2010 period. A first division of this data set following a topographical approach (continent vs. peripheral regions, with a 2,250 m topographical criterion) shows a high snowfall rate (275 mm yr at 1,200 m above ground level) with low relative seasonal variation ( ) over the peripheral areas. Over the plateau, the snowfall rate is low (34 mm yr at 1,200 m above ground level) with a much larger relative seasonal variation ( ). A second study that follows a geographical division highlights the average vertical structure of precipitation and temperature depending on the regions and their interactions with topography. In particular, over ice shelves, we see a strong dependence of the distribution of snowfall on the sea ice coverage. Finally, the relationship between precipitation and temperature is analyzed and compared with a simple analytical relationship. This study highlights that precipitation is largely dependent on the advection of air masses along the topographic slopes with an average vertical wind of 0.02 m s . This provides new diagnostics to evaluate climate models with a three-dimensional approach of the atmospheric structure of precipitation.
Keywords: Antarktis; global oppvarming; klimamodeller; klimatologi; meteorologi; nedbør; polarområdene; snøfall

Will Climate Change Impact Polar NOx Produced by Energetic Particle Precipitation? - Maliniemi, Ville; Marsh R., Daniel; Tyssøy, Hilde Nesse; Smith-Johnsen, Christine (Geophysical Research Letters, 2020)
Energetic electron precipitation (EEP) is an important source of polar nitrogen oxides (NOx) in the upper atmosphere. During winter, mesospheric NOx has a long chemical lifetime and is transported to the stratosphere by the mean meridional circulation. Climate change is expected to accelerate this circulation and therefore increase polar mesospheric descent rates. We investigate the Southern Hemispheric polar NOx distribution during the 21st century under a variety of future scenarios using simulations of the Whole Atmosphere Community Climate Model (WACCM). We simulate stronger polar mesospheric descent in all future scenarios that increase the atmospheric radiative forcing. Polar NOx in the upper stratosphere is significantly enhanced in two future scenarios with the largest increase in radiative forcing. This indicates that the ozone depleting NOx cycle will become more important in the future, especially if stratospheric chlorine species decline. Thus, EEP-related atmospheric effects may become more prominent in the future.
Keywords: Antarktis; geofysikk; klimaendringer; klimatologi; ozonlaget; polarområdene; romvitenskap

Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement - Nisbet, Euan G; Manning, Martin; Dlugokencky, Ed; Fisher, Rebecca; Lowry, Dave; Michel, Sylvia; Myhre, Cathrine Lund; Platt, Stephen Matthew; Allen, Grant; Bousquet, Philippe; Brownlow, Rebecca; Cain, Michelle; et al. (Global Biogeochemical Cycles, 2019)
Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1,775 ppb in 2006 to 1,850 ppb in 2017. Simultaneously the 13C/12C isotopic ratio (expressed as δ13CCH4) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained.
Keywords: Antarktis; atmosfæren; atmosfærisk metan; fossilt brensel; global klimamodell; global oppvarming; klimaendringer; klimagasser; metanisotoper; metanutslipp; meteorologi; polarområdene

Project and Community Management in Polar Sciences – Challenges and Opportunities - Werner, Kirstin; Zaika, Yulia; Pavlov, Alexey K; Lidström, Sven; Pope, Allen; Badhe, Renuka; Brückner, Marlen; Cristini, Luisa (Adv. Geosci., 2019)
Because geoscientific research often occurs via community-instigated bursts of activity with multi-investigator collaborations variously labelled as e.g., years (The International Polar Year IPY), experiments (World Ocean Circulation Experiment WOCE), programs (International Ocean Discovery Program), missions (CRYOSAT spacecraft), or decades (The International Decade of Ocean Exploration IDOE), successful attainment of research goals generally requires skilful scientific project management. In addition to the usual challenges of matching scientific ambitions to limited resources, on-going coordination and specifically project management, planning and implementation of polar science projects often involve many uncertainties caused by, for example, unpredictable weather or ocean and sea ice conditions, large-scale logistical juggling; and often these collaborations are spatially distributed and take place virtually. Large amounts of funding are needed to procure the considerable infrastructure and technical equipment required for polar expeditions; permissions to enter certain regions must be requested; and potential risks for expedition members as well as technical issues in extreme environments need to be considered. All these aspects are challenging for polar science projects, which therefore need a well thought-through program including a realistic alternative “plan B” and possibly also a “plan C” and “plan D”. The four most challenging overarching themes in polar science project management have been identified: international cooperation, interdisciplinarity, infrastructure, and community management. In this paper, we address ongoing challenges and opportunities in polar science project management based on a survey among 199 project and community managers and an additional of 85 project team members active in the field of polar sciences. Case studies and survey results are discussed with the conclusive goal to provide recommendations on how to fully reach the potential of polar sciences project and community management.
Keywords: Antarktis; geovitenskap; internasjonal samarbeid; klimaendringer; miljøendringer; polarområdene

SuperDARN Radar-Derived HF Radio Attenuation During the September 2017 Solar Proton Events - Bland, Emma C; Heino, Erkka; Kosch, Michael J; Partamies, Noora (Space Weather, 2018)
Two solar proton events in September 2017 had a significant impact on the operation of the Super Dual Auroral Radar Network (SuperDARN), a global network of high-frequency (HF) radars designed for observing F region ionospheric plasma convection. Strong polar cap absorption caused near-total loss of radar backscatter, which prevented the primary SuperDARN data products from being determined for a period of several days. During this interval, the high-latitude and polar cap radars measured unusually low levels of background atmospheric radio noise. We demonstrate that these background noise measurements can be used to observe the spatial and temporal evolution of the polar cap absorption region, using an approach similar to riometry. We find that the temporal evolution of the SuperDARN radar-derived HF attenuation closely follows that of the cosmic noise absorption measured by a riometer. Attenuation of the atmospheric noise up to 10 dB at 12 MHz is measured within the northern polar cap, and up to 14 dB in the southern polar cap, which is consistent with the observed backscatter loss. Additionally, periods of enhanced attenuation lasting 2–4 hr are detected by the midlatitude radars in response to M- and X-class solar flares. Our results demonstrate that SuperDARN's routine measurements of atmospheric radio noise can be used to monitor 8- to 20-MHz radio attenuation from middle to polar latitudes, which may be used to supplement riometer data and also to investigate the causes of SuperDARN backscatter loss during space weather events.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; ionosfæren; polarområdene; radiostøy

Provenance, transport and diagenesis of sediment in polar areas: a case study in Profound Lake, King George Island, Antarctica - Hernández, Ana C; Bastias, Joaquin; Matus, Daniela; Mahaney, William C (Polar Research, 2018)
Detailed scanning electron microscopy (SEM) micro-texture and mineralogical analysis of lacustrine sediment recovered from Profound Lake (also known as Uruguay Lake), Antarctica, was conducted in the foreland area of the Collins Glacier, King George Island. Very coarse and coarse sand grade size fractions (2 mm – 600 μm) were examined with SEM/ energy dispersive spectrometry, while the total sand fraction and fines (silt + clay) were examined using x-ray diffraction to determine relationships to source rock, weathering and transport history and long-term clay mineral weathering, all of which are poorly understood in polar areas. The mineralogy of these sediments was compared with petrographical information of the country rock to identify potential detrital sources. The association of recovered detrital minerals, sometimes strongly pre-weathered, supports release from source rock of basaltic and andesitic compositions. The micro-texture analysis of quartz, magnetite and various plagioclase grains show micro-features that reveal a complex weathering–diagenesis history tentatively extending into the Paleogene. The bedrock was eroded mostly by glacial processes and mechanical action presumed to result from glacial crushing. Alteration minerals, likely the product of pre-weathering, are probably sourced from weathered bedrock during contact with the sub-aerial atmosphere prior to entrainment. However, amorphous silica precipitation indicates weathering subsequent to glacial erosion from the source bedrock. Cracks of variable dimensions are mostly characteristic of either frost weathering or glacial transport, and involve mechanical and chemical processes.
Keywords: Antarktis; geologi; mineralogi; petrografi; polarområdene; sedimentologi

Mapping glacier-related research in polar regions: a bibliometric analysis of research output from 1987 to 2016 - Liang, Qi; Peng, Sha; Niu, Beibei; Zhou, Chunxia; Wang, Zhen (Polar Research, 2018)
We carried out a bibliometric analysis of literature related to glaciers in polar regions from the period 1987–2016 indexed in the Science Citation Index Expanded database. A comprehensive review was performed by analysing the research output trends, publication categories, main journals, leading countries and their collaborations, leading scientists, author keywords and Keywords Plus. The results indicated that the number of publications related to glaciers in polar regions has increased rapidly. The USA and several European countries, including the UK, France, Germany and Switzerland, are the leaders in the field of glacial studies, as reflected both in the productivity measures and in the distribution of core scientists. Quaternary Science Reviews, the Journal of Glaciology, and Geophysical Research Letters were the most productive journals for glacial studies. The synthesized analysis of the keywords demonstrated the current research emphases and hinted at future research trends. Reconstructing past climate changes through studies of ice-core records is one of the most important research subjects. Numerical modelling has become a commonly used tool in polar region glacial research. A better understanding of the responses of glaciers to widespread climatic warming is needed now and in the future.
Keywords: Antarktis; bibliometri; glasiologi; isbreer; klimaendringer; litteratur; miljøendringer; polarområdene

Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

Influence of meteorological parameters on atmospheric CO2 at Bharati, the Indian Antarctic research station - Pathakoti, Mahesh; Gaddamidi, Sreenivas; Gharai, Biswadip; Sudhakaran Syamala, Prijith; Venkata Narasimha Rao, Pamaraju; Choudhury, Saroj Bandh; Venkata Raghavendra, Kaila; Dadhwal, Vinay Kumar (Polar Research, 2018)
During the 35th Indian Scientific Expedition to Antarctica, measurements of atmospheric carbon dioxide (CO 2 ) were carried out using a Li-Cor CO 2 /H 2 O analyser at Bharati, the Indian Antarctic research station. This study examines the short-term variability of atmospheric CO 2 during the austral summer (January–February) of 2016. An average of 396.25 ± 4.20 ppm was observed during the study period. Meteorological parameters such as relative humidity, precipitation, wind speed, air temperature and atmospheric boundary layer height in conjunction with photosynthetically active radiation, the biological activity indicator which modulates atmospheric CO 2 concentration have been investigated. High wind speed (>20 m s −1 ) combined with precipitation scavenges CO 2 in the atmosphere, resulting in low concentrations at the study site. The lowest CO 2 concentration of 385 ppm coincided with heavy precipitation of 15 mm during study period. Statistical analysis of the data shows that precipitation and relative humidity independently correlated 55% (r = −0.55) and 32% (r = −0.32), respectively, with the variability of CO 2 mixing in the atmosphere at the study site. Atmospheric CO 2 was significantly correlated with precipitation alone with a p value of 0.003. Further, multiple regression analysis was performed to test the significant relation between variability of atmospheric CO 2 and meteorological parameters. Long-range air-mass transport analysis depicted that the majority of the air masses are reaching the study site through the oceanic region.
Keywords: Antarktis; atmosfæren; drivhuseffekt; drivhusgasser; forskning; karbondioksid; klimagasser; luftmassetransport; meteorologi; nedbør; polarområdene

Interhemispheric Survey of Polar Cap Aurora - Reidy, Jade; Fear, Robert; Whiter, Daniel; Lanchester, Betty; Kavanagh, Andrew John; Milan, Steve; Carter, Jennifer; Paxton, Larry; Zhang, Yongliang (Journal of Geophysical Research: Space Physics, 2018)
This study investigates the interhemispheric nature of polar cap auroras via ultraviolet imaging, combined with particle data, to determine whether they occur on open or closed field lines. Data from the SSUSI (Special Sensor Ultraviolet Spectrographic Imager) instrument on board the DMSP (Defence Meteorological Satellite Program) spacecraft are examined. The DMSP spacecraft are in 90-min orbits; hence, images of each hemisphere are separated by 45 min providing a good opportunity for interhemispheric study. 21 polar cap arc (PCA) events are recorded in December 2015 which have particle data from the SSJ/4 particle spectrometer associated with an arc in at least one hemisphere. Nine events are found to contain 'arcs' consistent with a closed field line mechanism, that is, arcs associated with an ion signature present in both hemispheres. Six events contained arcs that were consistent with an 'open field line' mechanism, that is, they were associated with electron-only precipitation. Events containing arcs that were not consistent with either of these expectations are also explored, including an example of a 'non-conjugate' theta aurora and an interesting example of auroral morphology similar to a PCA which is associated with a geomagnetic storm. Seasonal effects are also investigated through a statistical analysis of PCAs over 4 months in 2015. It is found that PCAs are visible in the SSUSI data at least 20% of the time and that it is likely some are missed due to the spacecraft field of view and poor sensitivity in the summer hemisphere due to increased solar illumination.
Keywords: Antarktis; astronomi; energiske partikler; geomagnetiske stormer; meteorologi; polarlys; polarområdene; solvind

Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Tourism and Arctic Observation Systems: exploring the relationships - de la Barre, Suzanne; Maher, Patrick; Dawson, Jackie; Hillmer-Pegram, Kevin; Huijbens, Edward; Lamers, Machiel; Liggett, Daniela; Müller, Dieter; Pashkevich, Albina; Stewart, Emma (Polar Research, 2016)
The Arctic is affected by global environmental change and also by diverse interests from many economic sectors and industries. Over the last decade, various actors have attempted to explore the options for setting up integrated and comprehensive trans-boundary systems for monitoring and observing these impacts. These Arctic Observation Systems (AOS) contribute to the planning, implementation, monitoring and evaluation of environmental change and responsible social and economic development in the Arctic. The aim of this article is to identify the two-way relationship between AOS and tourism. On the one hand, tourism activities account for diverse changes across a broad spectrum of impact fields. On the other hand, due to its multiple and diverse agents and far-reaching activities, tourism is also well-positioned to collect observational data and participate as an actor in monitoring activities. To accomplish our goals, we provide an inventory of tourism-embedded issues and concerns of interest to AOS from a range of destinations in the circumpolar Arctic region, including Alaska, Arctic Canada, Iceland, Svalbard, the mainland European Arctic and Russia. The article also draws comparisons with the situation in Antarctica. On the basis of a collective analysis provided by members of the International Polar Tourism Research Network from across the polar regions, we conclude that the potential role for tourism in the development and implementation of AOS is significant and has been overlooked. Keywords: Arctic; Antarctic; citizen science; observation systems; tourism; IPTRN
Keywords: Antarktis; klimaendringer; miljøendringer; polarområdene; turisme

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

The impact of sunlight on high-latitude equivalent currents - Laundal, Karl M; Gjerloev, Jesper; Østgaard, Nikolai; Reistad, Jone Peter; Haaland, Stein; Snekvik, Kristian; Tenfjord, Paul; Ohtani, Shin-ichi; Milan, Steve (Journal of Geophysical Research: Space Physics, 2016)
Ground magnetic field measurements can be mathematically related to an overhead ionospheric equivalent current. In this study we look in detail at how the global equivalent current, calculated using more than 30 years of SuperMAG magnetometer data, changes with sunlight conditions. The calculations are done using spherical harmonic analysis in quasi-dipole coordinates, a technique which leads to improved accuracy compared to previous studies. Sorting the data according to the location of the sunlight terminator and orientation of the interplanetary magnetic field (IMF), we find that the equivalent current resembles ionospheric convection patterns on the sunlit side of the terminator but not on the dark side. On the dark side, with southward IMF, the current is strongly dominated by a dawn cell and the current across the polar cap has a strong dawnward component. The contrast between the sunlit and dark side increases with increasing values of the F10.7 index, showing that increasing solar EUV flux changes not only the magnitude but also the morphology of the equivalent current system. The results are consistent with a recent study showing that Birkeland currents indirectly determine the equivalent current in darkness and that Hall currents dominate in sunlight. This has implication for the interpretation of ground magnetic field measurements and suggests that the magnetic disturbances at conjugate points will be asymmetrical when the solar illumination is different.
Keywords: Antarktis; geomagnetiske stormer; ionosfæren; ionosfæriske strømmer; polarlys; polarområdene; sollys; solvind

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

Den langsomme polare vippen - Sorokina, Svetlana (Naturen, 2016)
De siste 20 årene har vært de varmeste siden globale temperaturmålinger startet i 1880 (Figur 1). FNs klimapanel konkluderer med at hovedårsaken til den observerte temperaturøkningen er menneskeskapte utslipp av klimagasser. I nordområdene har temperaturen økt nesten dobbelt så raskt som i resten av verden. Isdekket er nær halvert og isvolumet er redusert til en tredjedel. Men på den andre siden av jorden, altså i Antarktis, er situasjonen en helt annen. Temperaturen har vært fallende de siste årene og isdekket har vært rekordstort. Dette paradokset brukes ofte som et argument mot menneskeskapte endring av klima. For hvordan kan det ha seg at temperaturen i Antarktis faller når klimagassutslippene øker?
Keywords: Antarktis; global oppvarming; klimaendringer; klimagasser; polarområdene

Advancements in decadal climate predictability: The role of nonoceanic drivers - Bellucci, Alessio; Haarsma, Rein; Bellouin, Nicolas; Booth, Ben B; Cagnazzo, Chiara; van den Hurk, Bart; Keenlyside, Noel; Koenigk, Torben; Massonnet, François; Materia, Stefano; Weiss, M (Reviews of Geophysics, 2015)
We review recent progress in understanding the role of sea ice, land surface, stratosphere, and aerosols in decadal-scale predictability and discuss the perspectives for improving the predictive capabilities of current Earth system models (ESMs). These constituents have received relatively little attention because their contribution to the slow climatic manifold is controversial in comparison to that of the large heat capacity of the oceans. Furthermore, their initialization as well as their representation in state-of-the-art climate models remains a challenge. Numerous extraoceanic processes that could be active over the decadal range are proposed. Potential predictability associated with the aforementioned, poorly represented, and scarcely observed constituents of the climate system has been primarily inspected through numerical simulations performed under idealized experimental settings. The impact, however, on practical decadal predictions, conducted with realistically initialized full-fledged climate models, is still largely unexploited. Enhancing initial-value predictability through an improved model initialization appears to be a viable option for land surface, sea ice, and, marginally, the stratosphere. Similarly, capturing future aerosol emission storylines might lead to an improved representation of both global and regional short-term climatic changes. In addition to these factors, a key role on the overall predictive ability of ESMs is expected to be played by an accurate representation of processes associated with specific components of the climate system. These act as “signal carriers,” transferring across the climatic phase space the information associated with the initial state and boundary forcings, and dynamically bridging different (otherwise unconnected) subsystems. Through this mechanism, Earth system components trigger low-frequency variability modes, thus extending the predictability beyond the seasonal scale.
Keywords: Sørishavet; geofysikk; havis; klimaendringer; klimamodeller; meteorologi; polarområdene; sjøis

On-site and in situ remediation technologies applicable to petroleum hydrocarbon contaminated sites in the Antarctic and Arctic - Camenzuli, Danielle; Freidman, Benjamin L (Polar Research, 2015)
Petroleum hydrocarbon contaminated sites, associated with the contemporary and legacy effects of human activities, remain a serious environmental problem in the Antarctic and Arctic. The management of contaminated sites in these regions is often confounded by the logistical, environmental, legislative and financial challenges associated with operating in polar environments. In response to the need for efficient and safe methods for managing contaminated sites, several technologies have been adapted for on-site or in situ application in these regions. This article reviews six technologies which are currently being adapted or developed for the remediation of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Bioremediation, landfarming, biopiles, phytoremediation, electrokinetic remediation and permeable reactive barriers are reviewed and discussed with respect to their advantages, limitations and potential for the long-term management of soil and groundwater contaminated with petroleum hydrocarbons in the Antarctic and Arctic. Although these technologies demonstrate potential for application in the Antarctic and Arctic, their effectiveness is dependent on site-specific factors including terrain, soil moisture and temperature, freeze–thaw processes and the indigenous microbial population. The importance of detailed site assessment prior to on-site or in situ implementation is emphasized, and it is argued that coupling of technologies represents one strategy for effective, long-term management of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Keywords: Petroleum hydrocarbons; remediation; Antarctica; Arctic; cold regions; contaminated site.
Keywords: Antarktis; forurensning; hydrokarboner; miljøvern; petroleum; polarområdene

Interhemispheric differences in ionospheric convection: Cluster EDI observations revisited - Förster, Matthias; Haaland, Stein (Journal of Geophysical Research: Space Physics, 2015)
The interaction between the interplanetary magnetic field and the geomagnetic field sets up a large-scale circulation in the magnetosphere. This circulation is also reflected in the magnetically connected ionosphere. In this paper, we present a study of ionospheric convection based on Cluster Electron Drift Instrument (EDI) satellite measurements covering both hemispheres and obtained over a full solar cycle. The results from this study show that average flow patterns and polar cap potentials for a given orientation of the interplanetary magnetic field can be very different in the two hemispheres. In particular during southward directed interplanetary magnetic field conditions, and thus enhanced energy input from the solar wind, the measurements show that the southern polar cap has a higher cross polar cap potential. There are persistent north-south asymmetries, which cannot easily be explained by the influence of external drivers. These persistent asymmetries are primarily a result of the significant differences in the strength and configuration of the geomagnetic field between the Northern and Southern Hemispheres. Since the ionosphere is magnetically connected to the magnetosphere, this difference will also be reflected in the magnetosphere in the form of different feedback from the two hemispheres. Consequently, local ionospheric conditions and the geomagnetic field configuration are important for north-south asymmetries in large regions of geospace.
Keywords: Antarktis; astrofysikk; geovitenskap; ionosfæren; magnetosfæren; polarområdene; solvind

Birkeland current effects on high-latitude ground magnetic field perturbations - Laundal, Karl M; Haaland, Stein; Lehtinen, N; Gjerloev, Jesper; Østgaard, Nikolai; Tenfjord, Paul; Reistad, Jone Peter; Snekvik, Kristian; Milan, Steve; Ohtani, Shin-ichi; Anderson, B J (Geophysical Research Letters, 2015)
Magnetic perturbations on ground at high latitudes are directly associated only with the divergence-free component of the height-integrated horizontal ionospheric current, J⊥,df. Here we show how J⊥,df can be expressed as the total horizontal current J⊥ minus its curl-free component, the latter being completely determined by the global Birkeland current pattern. Thus, in regions where J⊥=0, the global Birkeland current distribution alone determines the local magnetic perturbation. We show with observations from ground and space that in the polar cap, the ground magnetic field perturbations tend to align with the Birkeland current contribution in darkness but not in sunlight. We also show that in sunlight, the magnetic perturbations are typically such that the equivalent overhead current is antiparallel to the convection, indicating that the Hall current system dominates. Thus, the ground magnetic field in the polar cap relates to different current systems in sunlight and in darkness.
Keywords: Antarktis; Birkelandstrømmer; ionosfæren; ionosfæriske strømmer; polarområdene; sollys

Polychlorinated biphenyl exposure and corticosterone levels in seven polar seabird species - Tartu, Sabrina; Angelier, Frédéric; Bustnes, Jan-Ove; Moe, Børge; Hanssen, Sven Are; Herzke, Dorte; Gabrielsen, Geir Wing; Verboven, Nanette; Verreault, J; Labadie, Pierre; Budzinski, Helene; Wingfield, John C; et al. (Environmental Pollution, 2015)
The role of polychlorinated biphenyls (PCBs) on exposure-related endocrine effects has been poorly investigated in wild birds. This is the case for stress hormones including corticosterone (CORT). Some studies have suggested that environmental exposure to PCBs and altered CORT secretion might be associated. Here we investigated the relationships between blood PCB concentrations and circulating CORT levels in seven free-ranging polar seabird species occupying different trophic positions, and hence covering a wide range of PCB exposure. Blood ∑7PCB concentrations (range: 61–115,632 ng/g lw) were positively associated to baseline or stress-induced CORT levels in three species and negatively associated to stress-induced CORT levels in one species. Global analysis suggests that in males, baseline CORT levels generally increase with increasing blood ∑7PCB concentrations, whereas stress-induced CORT levels decrease when reaching high blood ∑7PCB concentrations. This study suggests that the nature of the PCB-CORT relationships may depend on the level of PCB exposure.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; polarområdene; sjøfugler; stresshormoner; zoologi

Corticosterone, prolactin and egg neglect behavior in relation to mercury and legacy POPs in a long-lived Antarctic bird - Tartu, Sabrina; Angelier, Frédéric; Wingfield, John C; Bustamante, Paco; Labadie, Pierre; Budzinski, Helene; Weimerskirch, Henri; Bustnes, Jan-Ove; Chastel, Olivier (Science of the Total Environment, 2015)
Seabirds often have high loads of contaminants. These contaminants have endocrine disrupting properties but their relationships with some endocrine mechanisms are still poorly investigated in free-living organisms. This is the case for the stress response which shifts energy investment away from reproduction and redirects it towards survival. In birds, this stress response is achieved through a release of corticosterone and is also accompanied by a decrease in circulating prolactin, an anterior pituitary hormone widely involved in regulating parental cares. We measured blood concentrations of some legacy persistent organic pollutants (POPs) and mercury (Hg) and examined their relationships with the corticosterone and prolactin responses of known-age (9–46years old) incubating snow petrels (Pagodroma nivea) to a standardized capture/handling stress protocol. In this Antarctic seabird, we also investigated whether high contaminant burden correlates with a higher occurrence of egg neglect, a frequently observed behavior in snow petrels. POPs and Hg were unrelated to age. Stress-induced corticosterone concentrations were positively related to POPs in both sexes, and stress-induced prolactin concentrations were negatively related to Hg in males. Egg-neglect behavior was not related to POPs burden, but males with higher Hg concentrations were more likely to neglect their egg. This suggests that in birds, relationships between age and contaminants are complex and that even low to moderate concentrations of POPs and Hg are significantly related to hormonal secretion. In this Antarctic species, exposure to legacy POPs and Hg could make individuals more susceptible to environmental stressors such as ongoing disturbances in Polar Regions.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; petreller; polarområdene; reproduksjon; sjøfugler; zoologi

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

Population-specific wintering distributions of adult south polar skuas over three oceans - Weimerskirch, Henri; Tarroux, Arnoud; Chastel, Olivier; Delord, Karine; Cherel, Yves; Descamps, Sébastien (Marine Ecology Progress Series, 2015)
Migratory routes and the areas used during winter have probably been selected to maximize fitness by providing favorable environmental conditions outside the breeding season. In polar environments, because of the extreme winter weather, most breeding species migrate to encounter better conditions in areas that can differ between and also within species. Using geolocation sensors, we found that south polar skuas Catharacta maccormicki from 2 distant populations breeding on the Antarctic continent along the Atlantic and Indian Oceans migrate northward to winter in tropical Indian Ocean and in temperate North Pacific waters, respectively. Most individuals from each population winter in different environmental conditions, with water temperatures ranging from 16 to 29°C. Nevertheless, they have very similar activity patterns, spending more than 80% of their time on the water, and their feather δ15N values suggest that they probably feed at similar trophic levels during the molt. During overwintering, the overall and constant low activity level may be partly imposed by molting constraints, but it also suggests that trophic conditions are good for skuas. The wintering areas of the species correspond to sectors of high concentrations of breeding or wintering tropical, Northern, and Southern Hemisphere seabird species that are likely to be kleptoparasitized by skuas. A certain degree of individual variation exists within each population, which induces a spatial overlap in the wintering grounds of distant breeding populations. These results have potential important consequences in terms of fitness, genetic divergence, and susceptibility to climate change and marine pollution. KEYWORDS: Catharacta maccormicki · Geolocators · Migration · Population-specific strategies · Stable isotopes.
Keywords: Dronning Maud Land; geolokalisering; klimaendringer; marin forurensning; ornitologi; polarområdene; trekkfugler; zoologi

Protists in the polar regions: comparing occurrence in the Arctic and Southern oceans using pyrosequencing - Wolf, Christian; Kilias, Estelle; Metfies, Katja (Polar Research, 2015)
In the ongoing discussion of the distribution of protists, whether they are globally distributed or endemic to one or both of the polar regions is the subject of heated debate. In this study, we compared next-generation sequencing data from the Arctic and the Southern oceans to reveal the extent of similarities and dissimilarities between the protist communities in the polar regions. We found a total overlap of operational taxonomic units (OTUs) between the two regions of 11.2%. On closer inspection of different taxonomic groups, the overlap ranged between 5.5% (haptophytes) and 14.5% (alveolates). Within the different groups, the proportion of OTUs occurring in both regions greatly differed between the polar regions. On the one hand, the overlap between these two regions is remarkable, given the geographical distance between them. On the other hand, one could expect a greater overlap of OTUs between these regions on account of the similar environmental conditions. The overlap suggests a connection between the polar regions for at least certain species or that the evolutionary divergence has been slow, relative to the timescales of isolation. The different proportions of common OTUs among the groups or regions may be a result of different life cycle strategies or environmental adaptations. Keywords: 18S rDNA; bipolar; next-generation sequencing; phytoplankton; polar regions; protist distribution.
Keywords: Sørishavet; fytoplankton; marin biologi; polarområdene; protoktister; pyrosekvensering; økosystemer

Commonness and rarity in the marine biosphere - Connolly, Sean R; MacNeil, M Aaron; Caley, M Julian; Knowlton, Nancy; Cripps, Ed; Hisano, Mizue; Thibaut, Loïc M; Bhattacharya, Bhaskar D; Benedetti-Cecchi, Lisandro; Brainard, Russell E; Brandt, Angelika; Bulleri, Fabio; et al. (Proceedings of the National Academy of Sciences, 2014)
Tests of biodiversity theory have been controversial partly because alternative formulations of the same theory seemingly yield different conclusions. This has been a particular challenge for neutral theory, which has dominated tests of biodiversity theory over the last decade. Neutral theory attributes differences in species abundances to chance variation in individuals’ fates, rather than differences in species traits. By identifying common features of different neutral models, we conduct a uniquely robust test of neutral theory across a global dataset of marine assemblages. Consistently, abundances vary more among species than neutral theory predicts, challenging the hypothesis that community dynamics are approximately neutral, and implicating species differences as a key driver of community structure in nature.Explaining patterns of commonness and rarity is fundamental for understanding and managing biodiversity. Consequently, a key test of biodiversity theory has been how well ecological models reproduce empirical distributions of species abundances. However, ecological models with very different assumptions can predict similar species abundance distributions, whereas models with similar assumptions may generate very different predictions. This complicates inferring processes driving community structure from model fits to data. Here, we use an approximation that captures common features of “neutral” biodiversity models—which assume ecological equivalence of species—to test whether neutrality is consistent with patterns of commonness and rarity in the marine biosphere. We do this by analyzing 1,185 species abundance distributions from 14 marine ecosystems ranging from intertidal habitats to abyssal depths, and from the tropics to polar regions. Neutrality performs substantially worse than a classical nonneutral alternative: empirical data consistently show greater heterogeneity of species abundances than expected under neutrality. Poor performance of neutral theory is driven by its consistent inability to capture the dominance of the communities’ most-abundant species. Previous tests showing poor performance of a neutral model for a particular system often have been followed by controversy about whether an alternative formulation of neutral theory could explain the data after all. However, our approach focuses on common features of neutral models, revealing discrepancies with a broad range of empirical abundance distributions. These findings highlight the need for biodiversity theory in which ecological differences among species, such as niche differences and demographic trade-offs, play a central role.
Keywords: Sørishavet; biodiversitet; biologi; marin økologi; marine økosystemer; polarområdene; zoologi

Contrasting strategies of resistance vs. tolerance to desiccation in two polar dipterans - Everatt, M J; Convey, P; Worland, M R; Bale, J S; Hayward, S A L (Polar Research, 2014)
Low water availability is one of the principal stressors for terrestrial invertebrates in the polar regions, determining the survival of individuals, the success of species and the composition of communities. The Arctic and Antarctic dipterans Heleomyza borealis and Eretmoptera murphyi spend the majority of their biennial life cycles as larvae, and so are exposed to the full range of environmental conditions, including low water availability, over the annual cycle. In the current study, the desiccation resistance and desiccation tolerance of larvae were investigated, as well as their capacity for cross-tolerance to temperature stress. Larvae of H. borealis showed high levels of desiccation resistance, only losing 6.9% of their body water after 12 days at 98.2% relative humidity (RH). In contrast, larvae of E. murphyi lost 46.7% of their body water after 12 days at the same RH. Survival of E. murphyi larvae remained high in spite of this loss (>80% survival). Following exposure to 98.2% RH, larvae of E. murphyi showed enhanced survival at −18°C for 2 h. The supercooling point of larvae of both species was also lowered following prior treatment at 98.2% RH. Cross-tolerance to high temperatures (37 or 38.5°C) was not noted following desiccation in E. murphyi, and survival even fell at 37°C following a 12-day pre-treatment. The current study demonstrates two different strategies of responding to low water availability in the polar regions and indicates the potential for cross-tolerance, a capacity which is likely to be beneficial in the ever-changing polar climate. Keywords: Acclimation; dipteran; supercooling point; temperature; cross-tolerance.
Keywords: Antarktis; diptera; polarområdene; temperatur; tovinger; uttørking; virvelløse dyr

Counteracting the climate effects of volcanic eruptions using short-lived greenhouse gases - Fuglestvedt, Jan S.; Samset, Bjørn H.; Shine, Keith P. (Geophysical Research Letters, 2014)
A large volcanic eruption might constitute a climate emergency, significantly altering global temperature and precipitation for several years. Major future eruptions will occur, but their size or timing cannot be predicted. We show, for the first time, that it may be possible to counteract these climate effects through deliberate emissions of short-lived greenhouse gases, dampening the abrupt impact of an eruption. We estimate an emission pathway countering a hypothetical eruption 3 times the size of Mount Pinatubo in 1991. We use a global climate model to evaluate global and regional responses to the eruption, with and without counteremissions. We then raise practical, financial, and ethical questions related to such a strategy. Unlike the more commonly discussed geoengineering to mitigate warming from long-lived greenhouse gases, designed emissions to counter temporary cooling would not have the disadvantage of needing to be sustained over long periods. Nevertheless, implementation would still face significant challenges.
Keywords: Antarktis; drivhusgasser; global klimamodell; global oppvarming; klimatologi; nedbør; polarområdene; vulkaner

Comparative study on PCDD/F pollution in soil from the Antarctic, Arctic and Tibetan Plateau - Jia, Shenglan; Wang, Qiang; Li, Li; Fang, Xuekun; Shi, Yehong; Xu, Weiguang; Hu, Jianxin (Science of the Total Environment, 2014)
The concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in 35 soil samples collected from Fildes Peninsula in the Antarctic, Ny-Ålesund in the Arctic, and Zhangmu-Nyalam in the Tibetan Plateau were reported in this study. A comparison of the total concentration and TEQ of PCDD/Fs at the Three Poles was conducted. Both the total concentration and TEQ of PCDD/Fs demonstrates a decreasing trend in the order of Zhangmu-Nyalam (mean: 26.22 pg/g, 0.37 pg I-TEQ/g)>Ny-Ålesund (mean: 9.97 pg/g, 0.33 pg I-TEQ/g)>Fildes Peninsula (mean: 2.18 pg/g, 0.015 pg I-TEQ/g) (p<0.05). In all samples, the congener and homologue profiles dominated with higher (seven and eight) chlorinated PCDD/Fs (more than 85% of the total mass percentage of PCDD/Fs) at the Three Poles. Finally, a FLEXPART backward simulation was used to preliminarily identify the potential local and regional anthropogenic sources of PCDD/Fs. The results imply that the air masses passing over surrounding regions with significant PCDD/F emissions might contribute to the occurrence of PCDD/Fs in both the Arctic and Tibetan Plateau.
Keywords: Antarktis; menneskelig påvirkning; miljøgifter; miljøovervåking; polarområdene

Verification of a new NOAA/NSIDC passive microwave sea-ice concentration climate record - Meier, Walter N; Peng, Ge; Scott, Donna J; Savoie, Matt H (Polar Research, 2014)
A new satellite-based passive microwave sea-ice concentration product developed for the National Oceanic and Atmospheric Administration (NOAA) Climate Data Record (CDR) programme is evaluated via comparison with other passive microwave-derived estimates. The new product leverages two well-established concentration algorithms, known as the NASA Team and Bootstrap, both developed at and produced by the National Aeronautics and Space Administration (NASA) Goddard Space Flight Center (GSFC). The sea-ice estimates compare well with similar GSFC products while also fulfilling all NOAA CDR initial operation capability (IOC) requirements, including (1) self-describing file format, (2) ISO 19115-2 compliant collection-level metadata, (3) Climate and Forecast (CF) compliant file-level metadata, (4) grid-cell level metadata (data quality fields), (5) fully automated and reproducible processing and (6) open online access to full documentation with version control, including source code and an algorithm theoretical basic document. The primary limitations of the GSFC products are lack of metadata and use of untracked manual corrections to the output fields. Smaller differences occur from minor variations in processing methods by the National Snow and Ice Data Center (for the CDR fields) and NASA (for the GSFC fields). The CDR concentrations do have some differences from the constituent GSFC concentrations, but trends and variability are not substantially different. Keywords: Sea ice; Arctic and Antarctic oceans; climate data record; evaluation; passive microwave remote sensing.
Keywords: Sørishavet; evaluering; havis; klimaendringer; polarområdene; sjøis

On-site and in situ remediation technologies applicable to metal-contaminated sites in Antarctica and the Arctic: a review - Camenzuli, Danielle; Freidman, Benjamin L; Statham, Tom M; Mumford, Kathryn A; Gore, Damian B (Polar Research, 2013)
Effective management of contaminated land requires a sound understanding of site geology, chemistry and biology. This is particularly the case for Antarctica and the Arctic, which function using different legislative frame- works to those of industrialized, temperate environments and are logistically challenging environments to operate in. This paper reviews seven remediation technologies currently used, or demonstrating potential for on-site or in situ use at metal-contaminated sites in polar environments, namely permeable reactive barriers (PRB), chemical fixation, bioremediation, phytoremediation, electrokinetic separation, land capping, and pump and treat systems. The technologies reviewed are discussed in terms of their advantages, limitations and overall potential for the management of metal-contaminated sites in Antarctica and the Arctic. This review demonstrates that several of the reviewed technologies show potential for on-site or in situ usage in Antarctica and the Arctic. Of the reviewed technologies, chemical fixation and PRB are particularly promising technologies for metal-contaminated sites in polar environments. However, further research and relevant field trials are required before these technologies can be considered proven techniques. Keywords: Polar; heavy metals; remediation; contaminants; in situ
Keywords: Antarktis; biologi; forurensning; geologi; jord; kjemi; menneskelig påvirkning; polarområdene; tungmetaller

The impact of abrupt suspension of solar radiation management (termination effect) in experiment G2 of the Geoengineering Model Intercomparison Project (GeoMIP) - Jones, Andy; Haywood, Jim M; Alterskjær, Kari; Boucher, Olivier; Cole, Jason N S; Curry, Charles L; Irvine, Peter J; Ji, Duoying; Kravitz, Ben; Egill Kristjánsson, Jón; Moore, John C; Niemeier, Ulrike; et al. (Journal of Geophysical Research: Atmospheres, 2013)
We have examined changes in climate which result from the sudden termination of geoengineering after 50 years of offsetting a 1% per annum increase in CO2 concentrations by a reduction of solar radiation, as simulated by 11 different climate models in experiment G2 of the Geoengineering Model Intercomparison Project. The models agree on a rapid increase in global-mean temperature following termination accompanied by increases in global-mean precipitation rate and decreases in sea-ice cover. There is no agreement on the impact of geoengineering termination on the rate of change of global-mean plant net primary productivity. There is a considerable degree of consensus for the geographical distribution of temperature change following termination, with faster warming at high latitudes and over land. There is also considerable agreement regarding the distribution of reductions in Arctic sea-ice, but less so for the Antarctic. There is much less agreement regarding the patterns of change in precipitation and net primary productivity, with a greater degree of consensus at higher latitudes.
Keywords: Antarktis; global oppvarming; karbondioksid; klimaendringer; klimamodeller; klimatologi; polarområdene; solstråling

Standardized algal growth potential and/or algal primary production rates of maritime Antarctic stream waters (King George Island, South Shetlands) - Kvíderová, Jana; Elster, Josef (Polar Research, 2013)
In addition to the chemical analyses providing total nutrient content, standardized water trophic status bioassays are useful in the determination of available nutrients for primary producers. The aim of the study was to determine the standardized values of algal growth potential (AGP) and algal primary productivity rate (APPR) of maritime Antarctic stream water using modified AGP/APPR protocols. The standardized values of AGP and the APPR of oligotrophic and mesotrophic water samples from snow-melt streams were measured, and possible nutrient limitation and heavy metal inhibition were evaluated at 5°C and 25°C using polar and temperate strains of Stichococcus bacillaris, respectively. The water samples were enriched for the nutrient limitation tests with 1000 mμ l-1 NO3- -N, 50 μg l-1 PO43- -P, and a mixture of 1000 μg l-1 NO3- -N + 50 μg l-1 PO43- -P, and for the heavy metal inhibition tests with 1000 mg l-1 Na2-ethylenediaminetetraacetic acid (EDTA). The AGP of oligotrophic samples was significantly lower than that of the mesotrophic ones at both temperatures. In addition, AGP was significantly higher at 5°C than at 25°C. Oligotrophic samples were identified as being nitrogen limited, while no nutrient limitation was observed in the mesotrophic samples. No statistically significant heavy metal inhibition was observed at either temperature. The positive correlation of AGP and water nutrient content indicates that the method used accurately and comprehensively monitors the changes in biological availability of mineral nutrients and can provide a standardized reference point for similar exploration of freshwater ecosystems across both polar regions. Keywords: Maritime Antarctic; microalgae; nutrient limitations; snow-melt stream water.
Keywords: Antarktis; alger; analyser; ferskvann; innsjø; kjemisk; klimaendringer; næringsstoff; polarområdene; snø; strøm; økosystemer

Automated ice-sheet snowmelt detection using microwave radiometer measurements - Liang, Lei; Guo, Huadong; Li, Xinwu; Cheng, Xiao (Polar Research, 2013)
Monitoring ice-sheet snowmelt is fundamental to understanding global climate change. A simple and automated snowmelt detection process is critical to the establishment of an ice-sheet snowmelt monitoring system. However, different ice-sheet snowmelt detection methods are based on a variety of thresholding schemes using different melt signals for dry and wet snow; these complicate the regular operation of an ice-sheet snowmelt monitoring. We propose an automated melt signal detection method developed using melt signals derived from the cross-gradient polarization ratio snowmelt detection method over Greenland and the wavelet transformation-based snowmelt detection method over Antarctica. Initial results indicate that the proposed method not only increases computational efficiency, practicability and operability but is also more accurate. Keywords: Ice sheet; snowmelt detection; radiometer; cross-gradient polarization ratio; wavelet transformation; generalized Gaussian model.
Keywords: Antarktis; innlandsis; klimaendringer; mikrobølge; målinger; polarområdene; radiometer; snøsmelting; statistisk analyse; temperatur måling

Observations of nitric oxide in the Antarctic middle atmosphere during recurrent geomagnetic storms - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Straub, Corinne; Holmén, Kim; Horne, Richard B (Journal of Geophysical Research: Space Physics, 2013)
We report ground-based measurements of the polar middle atmosphere made using a 230–250 GHz passive microwave radiometer deployed at Troll station (72°01′S 02°32′E, L shell of L = 4.8), Antarctica. Our observations show enhanced mesospheric nitric oxide (NO) volume mixing ratio (VMR) during a series of small recurrent geomagnetic storms in the 2008 austral winter, reaching 1.2 ppmv on day 200 (18 July). The Lomb normalized periodogram of the NO VMR time series averaged over 65-80 km for days 130 to 220 of 2008 (9 May to 7 August) shows a peak exceeding the 95% confidence limit at 25.8 days, close to the synodic rotation period for low-latitude solar coronal holes. The highest correlations between the radiometer NO VMR data and trapped and quasi-trapped electron count rates for L = 3.5-5.5 from the Polar Orbiting Environment Satellites 90° telescope are for the >30 keV (90e1) channel (rmax = 0.56, lag time of 5.1 days) and >100 keV (90e2) channel (rmax = 0.57, lag time of 4.4 days). Maximum correlation between NO VMR and the >700 keV (90P6) channel data is lower but lag times are close to zero. Superposed epoch analyses for the eight most significant geomagnetic storm periods and three Carrington rotations (2070-2072) within the 90 day observation period indicate that significant NO abundance observed at 65-80 km in the Antarctic mesosphere may be produced directly by >200 keV electron precipitation or originate from a source at higher altitudes, e.g., production by >30 keV electrons followed by downward transport.
Keywords: Antarktis; atmosfæren; fysikk; geomagnetiske stormer; meteorologi; polarområdene

Arctic and Antarctic sea ice acts as a sink for atmospheric CO2 during periods of snowmelt and surface flooding - Nomura, Daiki; Granskog, Mats A; Assmy, Philipp; Simizu, Daisuke; Hashida, Gen (Journal of Geophysical Research: Oceans, 2013)
In this study, we present evidence that Antarctic and Arctic sea ice act as sink for atmospheric CO2 during periods of snowmelt and surface flooding. The CO2 flux measured directly at the flooded sea ice surface (Fflood) constituted a net CO2 sink of −1.1 ± 0.9 mmol C m−2 d−1 (mean ± 1 SD), which was an order of magnitude higher than the flux measured at the snow-air surface (Fsnow) and bare ice surface (Fice). The Fsnow/Fflood ratio decreased with increasing water equivalent of snow and superimposed-ice, suggesting that the properties of snow and superimposed-ice formation affect the magnitude of the CO2 flux. The Fsnow/Fflood ratio ranged from 0.1 to 0.5, illustrating that 50–90% of the potential flux at the flooded surface was reduced due to the presence of snow/superimposed-ice. Hence, snow cover properties and superimposed-ice play an important role in the CO2 fluxes across the sea ice-snow-atmosphere interface.
Keywords: Sørishavet; atmosfæren; gassutveksling; havis; karbondioksid; klimaendringer; klimatologi; meteorologi; polarområdene; sjøis

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Can we use ice sheet reconstructions to constrain meltwater for deglacial simulations? - Bethke, Ingo; Li, Camille; Nisancioglu, Kerim H (Paleoceanography, 2012)
Freshwater pulses from melting ice sheets are thought to be important for driving deglacial climate variability. This study investigates challenges in simulating and understanding deglacial climate evolution within this framework, with emphasis on uncertainties in the ocean overturning sensitivity to meltwater inputs. The response of an intermediate complexity model to a single Northern Hemisphere meltwater pulse is familiar: a weakening of the ocean overturning circulation in conjunction with an expansion of sea ice cover and a meridional temperature seesaw. Nonlinear processes are vital in shaping this response and are found to have a decisive influence when more complex scenarios with a history of pulses are involved. A meltwater history for the last deglaciation (21–9 ka) was computed from the ICE-5G ice sheet reconstruction, and the meltwater was routed into the ocean through idealized ice sheet drainages. Forced with this meltwater history, model configurations with altered freshwater sensitivity produce a range of outcomes for the deglaciation, from those in which there is a complete collapse of the overturning circulation to those in which the overturning circulation weakens slightly. The different outcomes are interpreted in terms of the changing hysteresis behavior of the overturning circulation (i.e., non-stationary freshwater sensitivity) as the background climate warms through the course of the deglaciation. The study illustrates that current uncertainties in model sensitivity are limiting in efforts to forward-model deglacial climate variability. Furthermore, ice sheet reconstructions are shown to provide poor constraints on meltwater forcing for simulating the deglaciation.
Keywords: Sørishavet; global oppvarming; havnivåstigning; innlandsis; isavsmelting; klimamodeller; klimatologi; polarområdene; smeltevann

Aerosol-Mediated Transport and Deposition of Brominated Diphenyl Ethers to Antarctica - Dickhut, Rebecca M; Cincinelli, Alessandra; Cochran, Michele; Kylin, Henrik (Environmental Science & Technology, 2012)
Brominated diphenyl ethers (BDE47, 99, 100, and 209) were measured in air, snow and sea ice throughout western Antarctica between 2001 and 2007. BDEs in Antarctic air were predominantly associated with aerosols and were low compared to those in remote regions of the northern hemisphere, except in Marguerite Bay following the fire at Rothera research station in Sept 2001, indicating that this event was a local source of BDE209 to the Antarctic environment. Aerosol BDE47/100 reflects a mixture of commercial pentaBDE products; however, BDE99/100 is suggestive of photodegradation of BDE99 during long-range atmospheric transport (LRAT) in the austral summer. BDEs in snow were lower than predicted based on snow scavenging of aerosols indicating that atmospheric deposition events may be episodic. BDE47, -99, and -100 significantly declined in Antarctic sea ice between 2001 and 2007; however, BDE209 did not decline in Antarctic sea ice over the same time period. Significant losses of BDE99 and -100 from sea ice were recorded over a 19 day period in spring 2001 demonstrating that seasonal ice processes result in the preferential loss of some BDEs. BDE47/100 and BDE99/100 in sea ice samples reflect commercial pentaBDE products, suggesting that photodegradation of BDE99 is minimal during LRAT in the austral winter.
Keywords: Antarktis; Sørishavet; atmosfæren; forurensning; miljøgifter; polarområdene

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

Polar operations in Antarctica – operating the Troll Research Station, Dronning Maud Land - Mikelborg, Øystein; Pedersen, Ken (Fram forum, 2012)
Keywords: Dronning Maud Land; Troll forskningsstasjon; ekspedisjoner; logistikk; polarområdene

Being there: examining the behaviour of Antarctic tourists through their blogs - Roura, Ricardo M (Polar Research, 2012)
Most visitors to Antarctica today are commercial tourists. Over 150 000 tourists visited Antarctica between 2007 and 2010, making up more than 700 000 person/landings. Despite the scale of tourism in Antarctica, knowledge about its environmental impacts is generally inconclusive, and monitoring is limited. This article examines tourist behaviour regarding the environment using information available on travel weblogs (blogs) posted by tourists on the Internet. Fifty blogs describing Antarctic travel were analysed, mostly as part of organized tourism cruises, during the four Antarctic summer seasons between 2007 and 2010, both qualitatively and quantitatively. The blogs described the activities of 90 people who had visited Deception Island as part of their itinerary and who, overall, had undertaken at least 190 person/landings in Antarctica. Blog analysis highlighted the importance of wildlife as a tourist attraction. In the blogs it was apparent that touristwildlife interactions result in a range of behaviours from both individual tourists and animals. Tourism results in cultural traces and other environmental consequences, although some of these would not be judged as ‘‘impacts’’ under the current practice of implementing the Protocol on Environmental Protection to the Antarctic Treaty. Blogs showed many more instances of compliance than of noncompliance with environmental regulations. Tourist blogs illustrate the behavioural processes by which environmental impacts from tourism could occur, which are repeated through thousands of person-landings and other activities in Antarctica every season. Precautionary action may be a practical alternative to manage tourism at some sites until it is clearer how this activity affects the environment.
Keywords: Antarktis; miljøvern; polarområdene; turisme

Foreword: The complex business of managing human activities and protecting the environment of the polar regions - Tin, Tina; Liggett, Daniela; Maher, Patrick T (Polar Research, 2012)
The thematic cluster ‘‘Human impacts in the Arctic and Antarctic’’ in Polar Research has its origins in the International Polar Year (2007-09) Oslo Science Conference held in Oslo, Norway, from 8 to 12 June 2010. We were the co-convenors of the session ‘‘Human impacts in the Arctic and Antarctic: regulatory and management implications,’’ in which 27 talks and 21 posters were presented over the course of two days. We invited contributors to the conference session to explore all types of impacts of human activities and regional environmental change in the polar regions, with a special focus on highlighting the management priorities for the protection of the landscape (environment and people) of the polar regions in the face of increasing human activity. Exploring a wide range of topics ranging from human wildlife interactions to chemical contamination and from whaling to polar tourism, contributors provided examples of existing environmental management regimes that are working as well as those that are not.
Keywords: Antarktis; forurensning; menneskelig påvirkning; miljøvern; polarområdene; turisme; økosystemer

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Review of Tourism and change in polar regions: climate, environment and experience and Cruise tourism in polar regions: promoting environmental and social sustainability? - Capelotti, P J (Polar Research, 2011)
These two edited volumes, which cover much of the same ground, both begin from a common premise: polar tourism, as its been experienced by wealthy travellers for over a century, has a very definite shelf life. With the acceleration of global climate change, the Arctic and Antarctic are being changed, changed rapidly, perhaps permanently and, if one pays attention to the news, seemingly by the day. When combined with popular documentaries and feature films like An inconvenient truth, March of the penguins and Happy feet potential polar tourists have been sensitized to see the polar regions not as implacably hostile wastes once challenged only by the likes of Nansen, Amundsen, Scott and Shackleton but as irreplaceably fragile zones that, once lost, will take some essential part of the planet with them.
Keywords: Antarktis; bokanmeldelser; cruiseturisme; global oppvarming; klimaendringer; miljøvern; polarområdene; turisme; økologi

Princess Elisabeth Antarctica: an International Polar Year outreach and media success story - Cheek, Joseph; Huyge, Ben; Pomereu, Jean de (Polar Research, 2011)
One of the priorities of the fourth International Polar Year (IPY) was to increase awareness of the polar regions and polar science among the general public through education, communication and other forms of outreach. This paper reports on the media coverage of Princess Elisabeth Antarctica (PEA), Belgium’s ‘‘zero-emission’’ Antarctic research station designed by the nonprofit International Polar Foundation (IPF) to run on wind and solar energy and to employ state-of-the-art forms of energy management and other ‘‘green’’ technology. This paper provides background information on PEA, a review of IPF’s media strategy for the project, a description of media coverage of the station and a discussion of the way in which the IPF’s main messages were reported in the media. IPF staff surveyed approximately 300 media reports released between February 2004, when the PEA project was announced to the general public, and June 2010, when the IPF presented their findings at the IPY conference in Oslo. PEA was featured 580 times in print and web media in Belgium, and 303 times outside Belgium. Major international agencies such as the Associated Press, Agence France Presse, the BBC, Al-Jazeera and Reuters covered the project. On television and radio, PEA was featured in news broadcasts from all four major television networks in Belgium, most major radio stations and 34 different television and radio news outlets outside Belgium. The paper concludes that the media coverage for PEA was significant and suggests reasons why the project was so widely reported. Keywords: Media and outreach; media strategy; Antarctic research stations; energy management system; renewable energy; reducing environmental footprint
Keywords: Antarktis; Det internasjonale polaråret; fornybar energi; forskningsstasjoner; fotavtrykk; mediadekning; miljø; polarområdene

Polythermal glacier hydrology: a review - Irvine-Fynn, Tristram D L; Hodson, Andrew J; Moorman, Brian J; Vatne, Geir; Hubbard, Alun L (Reviews of Geophysics, 2011)
The manner by which meltwater drains through a glacier is critical to ice dynamics, runoff characteristics, and water quality. However, much of the contemporary knowledge relating to glacier hydrology has been based upon, and conditioned by, understanding gleaned from temperate valley glaciers. Globally, a significant proportion of glaciers and ice sheets exhibit nontemperate thermal regimes. The recent, growing concern over the future response of polar glaciers and ice sheets to forecasts of a warming climate and lengthening summer melt season necessitates recognition of the hydrological processes in these nontemperate ice masses. It is therefore timely to present an accessible review of the scientific progress in glacial hydrology where nontemperate conditions are dominant. This review provides an appraisal of the glaciological literature from nontemperate glaciers, examining supraglacial, englacial, and subglacial environments in sequence and their role in hydrological processes within glacierized catchments. In particular, the variability and complexity in glacier thermal regimes are discussed, illustrating how a unified model of drainage architecture is likely to remain elusive due to structural controls on the presence of water. Cold ice near glacier surfaces may reduce meltwater flux into the glacier interior, but observations suggest that the transient thermal layer of near surface ice holds a hydrological role as a depth-limited aquifer. Englacial flowpaths may arise from the deep incision of supraglacial streams or the propagation of hydrofractures, forms which are readily able to handle varied meltwater discharge or act as locations for water storage, and result in spatially discrete delivery of water to the subglacial environment. The influence of such drainage routes on seasonal meltwater release is explored, with reference to summer season upwellings and winter icing formation. Moreover, clear analogies emerge between nontemperate valley glacier and ice sheet hydrology, the discussion of which indicates how persistent reassessment of our conceptualization of glacier drainage systems is required. There is a clear emphasis that continued, integrated endeavors focused on process glaciology at nontemperate glaciers are a scientific imperative to augmenting the existing body of research centered on ice mass hydrology.
Keywords: Antarktis; geografi; glasiologi; global oppvarming; hydrologi; innlandsis; isbreer; isbrem; polarområdene

Low-ozone events in the southern polar summer as indicated by Met Office ozone analyses - Jackson, David; Orsolini, Yvan Joseph; Engelsen, Ola (Journal of Geophysical Research: Atmospheres, 2011)
Southern summer low-ozone events (LOEs) are examined using Met Office ozone analyses for 2005–2007. At 31 hPa, tongues of low-ozone air are pulled out of the polar region and extend to lower latitudes. Low tongues are also seen at 100 hPa, but there the low ozone is transported from low to high latitudes. These low tongues are frequently superimposed on one another, meaning that there are often also reductions in total ozone. What is striking is that at high latitudes, summer total ozone is typically lower over the Weddell Sea than at other longitudes. The low-ozone tongues at 31 and 100 hPa are consistent with transport associated with planetary waves. Daily geopotential height fields show a poleward and westward wave tilt with height, indicating the presence of baroclinic waves. The tilt enables the superimposition of the low-ozone tongues at 100 and 31 hPa. Filtered geopotential height anomalies reveal the presence of waves reported in other studies and indicate the connection between tropospheric and stratospheric wave dynamics in driving the LOEs. There is also a high connection between the LOEs and ultraviolet (UV) Index. The Weddell Sea region gets up to 20–30% more UV than the zonal mean, and the tip of South America gets about 10–25% more. There have been numerous studies of the impacts of increased UV on the Antarctic marine ecosystem during the springtime ozone hole, and our results indicate there is a case for these studies being extended to the summer LOEs.
Keywords: Antarktis; UV-stråling; Weddellhavet; ozonlaget; polarområdene; stratosfæren; ultrafiolett stråling

Pitfalls in radar diagnosis of ice-sheet bed conditions: Lessons from englacial attenuation models - Matsuoka, Kenichi (Geophysical Research Letters, 2011)
Radar power returned from ice-sheet beds has been widely accepted as an indicator of bed conditions. However, the bed returned power also depends on englacial attenuation, which is primarily a function of ice temperature. Here, using a one-dimensional attenuation model, it is demonstrated that, in most cases, variations in bed returned power are dominated by variations in englacial attenuation, rather than bed reflectivity. Both accumulation rate and geothermal flux anomalies can interfere with the interpretation. With the consequence, analytical radar algorithms that have been widely accepted likely yield false delineations of wet/dry beds. More careful consideration is needed when diagnosing bed conditions. Spatial patterns of shallow englacial radar reflectors can be used as a proxy for accumulation rates, which affect ice temperature and thus returned power. I argue that it is necessary to simultaneously interpret the returned power and englacial-reflector patterns to improve the bed diagnosis.
Keywords: Antarktis; geotermisk strømning; glasiologi; innlandsis; istykkelse; overflateakkumulering; polarområdene

Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene

An extreme precipitation event in Dronning Maud Land, Antarctica: a case study with the Antarctic Mesoscale Prediction System - Schlosser, Elisabeth; Powers, Jordan G.; Duda, Michael G.; Manning, Kevin W.; Reijmer, Carleen H.; van den Broeke, Michiel R. (Polar Research, 2010)
An extreme precipitation event that influenced almost the whole polar plateau of Dronning Maud Land, Antarctica, is investigated using Antarctic Mesoscale Prediction System archive data. For the first time a high-resolution atmospheric model especially adapted for polar regions was used for such a study in Dronning Maud Land. The outstanding event of 21–25 February 2003 was connected to a strong north-westerly flow, caused by a blocking high above eastern Dronning Maud Land, that persisted for several days and brought unusually large levels of moisture to the Antarctic Plateau. This weather situation is most effective in bringing precipitation to high-altitude interior Antarctic ice-core drilling sites, where precipitation in the form of diamond dust usually dominates. However, a few such precipitation events per year can account for a large percentage of the annual accumulation, which can cause a strong bias in ice-core data. Additionally, increased temperatures and wind speeds during these events need to be taken into account for the correct climatic interpretation of ice cores. A better understanding of the frequency of occurrence of intermittent precipitation in the interior of Antarctica in past and future climates is necessary for both palaeoclimatological studies and estimates of future sea-level change.
Keywords: Dronning Maud Land; havnivåstigning; klimaendringer; klimatologi; meteorologi; nedbør; polarområdene

Characteristics of atmospheric transport into the Antarctic troposphere - Stohl, Andreas; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2010)
We have developed a 5.5 year climatology of atmospheric transport into the Antarctic troposphere, which uses the same data set and methods as described in a recent study for the Arctic. This allows direct comparisons of transport properties for the two polar regions. The climatology is based on a simulation with the Lagrangian particle dispersion model FLEXPART, where the model atmosphere was globally filled with particles. Transport characteristics as well as emission sensitivities were derived from 6 hourly particle positions. We found that the probability for near-surface air to originate from the stratosphere on a time scale of 10 days is an order of magnitude higher near the South Pole than near the North Pole, a result of higher topography and descent that partly compensates for the flow of air down the Antarctic Plateau with the katabatic winds. The stratospheric influence is largest in fall, which is opposite to the seasonality in the Arctic. Stratospheric influence is much smaller over the shelf ice regions and in a band around Antarctica. The average time for which air near the surface has been exposed to continuous darkness in July (continuous light in January) is longest over the Ronne Ice Shelf and Ross Ice Shelf at ∼11 days (20 days). We calculated how sensitive Antarctic air masses are to emission input up to 30 days before arriving in Antarctica if removal processes are ignored. The emission sensitivity shows strong meridional gradients and, as a result, is generally low over South America, Africa, and Australia. For a 10 day time scale, the largest emission sensitivities over these continents are 1–2 orders of magnitude smaller than over Eurasia for transport to the Arctic, showing that foreign continents have a much smaller potential to pollute the Antarctic than the Arctic troposphere. Emission sensitivities and derived black carbon (BC) source contributions over South America, Africa, and Australia are substantially (a factor 10 for Africa) larger in winter than in summer. In winter, biomass burning contributes more BC than anthropogenic sources. For typical aerosol lifetimes of 5–10 days, ship emissions south of 60°S account for half of the total BC concentrations in the lowest 1000 m of the atmosphere south of 70°S in December. The increasing number of tourists visiting Antarctica and fishing vessels operating close to Antarctica are, therefore, a matter of concern.
Keywords: Antarktis; cruiseturisme; forurensning; klimatologi; polarområdene; stratosfæren; utslipp

Contrasting climate change in the two polar regions - Turner, John; Overland, Jim (Polar Research, 2009)
The two polar regions have experienced remarkably different climatic changes in recent decades. The Arctic has seen a marked reduction in sea-ice extent throughout the year, with a peak during the autumn. A new record minimum extent occurred in 2007, which was 40% below the long-term climatological mean. In contrast, the extent of Antarctic sea ice has increased, with the greatest growth being in the autumn. There has been a large-scale warming across much of the Arctic, with a resultant loss of permafrost and a reduction in snow cover. The bulk of the Antarctic has experienced little change in surface temperature over the last 50 years, although a slight cooling has been evident around the coast of East Antarctica since about 1980, and recent research has pointed to a warming across West Antarctica. The exception is the Antarctic Peninsula, where there has been a winter (summer) season warming on the western (eastern) side. Many of the different changes observed between the two polar regions can be attributed to topographic factors and land/sea distribution. The location of the Arctic Ocean at high latitude, with the consequently high level of solar radiation received in summer, allows the icealbedo feedback mechanism to operate effectively. The Antarctic ozone hole has had a profound effect on the circulations of the high latitude ocean and atmosphere, isolating the continent and increasing the westerly winds over the Southern Ocean, especially during the summer and winter.
Keywords: Antarktis; Sørishavet; havis; klimaendringer; klimatologi; ozonhull; ozonlaget; polarområdene; sjøis

Self-scattering of a powerful HF radio wave on stimulated ionospheric turbulence - Zalizovski, Andriy; Kashcheyev, S B; Yampolski, Y M; Galushko, V G; Belyey, Vasyl; Isham, B; Rietveld, M T; La Hoz, C; Brekke, A; Blagoveshchenskaya, N F; Kornienko, V A (Radio Science, 2009)
An analysis is presented of high-frequency (HF) signals from the European Incoherent Scatter HF ionospheric modification transmitter received during 26–30 October 2002 at three sites, two in Europe and one in Antarctica. Two components with different characteristics (“mirror-reflected” and “scattered”) were observed in the signal spectra. The mirror-reflected component can be associated with radiation through the side lobes of the transmitting antenna thus bypassing the modified volume on its way to the receiving sites. In contrast, the scattered component was radiated through the main antenna beam and then scattered by pump-induced ionospheric irregularities above the heater. As a result, variations in the scattered component signal intensity and Doppler frequency shifts (DFS) recorded at the greatly separated sites showed a high level of correlation. It is shown that the Doppler frequency variations can be associated with variations in the plasma density and/or physical motion velocities of stimulated inhomogeneities within the volume common to all propagation paths. Analysis of Doppler frequency shifts at greatly separated sites would allow identifying the mechanism responsible for the self-scattering effect. In the case of DFSs due to motion of the pump-induced scatterers it would be also possible to reconstruct the full velocity vector of the inhomogeneities.
Keywords: Antarktis; astronomi; fysikk; ionosfæren; polarområdene

Southern Ocean frontal structure and sea-ice formation rates revealed by elephant seals - Charrassin, J.-B.; Hindell, M.; Rintoul, S. R.; Roquet, F.; Sokolov, S.; Biuw, M.; Costa, D.; Boehme, L.; Lovell, P.; Coleman, R.; Timmermann, R.; Meijers, A.; et al. (Proceedings of the National Academy of Sciences, 2008)
Polar regions are particularly sensitive to climate change, with the potential for significant feedbacks between ocean circulation, sea ice, and the ocean carbon cycle. However, the difficulty in obtaining in situ data means that our ability to detect and interpret change is very limited, especially in the Southern Ocean, where the ocean beneath the sea ice remains almost entirely unobserved and the rate of sea-ice formation is poorly known. Here, we show that southern elephant seals (Mirounga leonina) equipped with oceanographic sensors can measure ocean structure and water mass changes in regions and seasons rarely observed with traditional oceanographic platforms. In particular, seals provided a 30-fold increase in hydrographic profiles from the sea-ice zone, allowing the major fronts to be mapped south of 60°S and sea-ice formation rates to be inferred from changes in upper ocean salinity. Sea-ice production rates peaked in early winter (April?May) during the rapid northward expansion of the pack ice and declined by a factor of 2 to 3 between May and August, in agreement with a three-dimensional coupled ocean?sea-ice model. By measuring the high-latitude ocean during winter, elephant seals fill a ?blind spot? in our sampling coverage, enabling the establishment of a truly global ocean-observing system.
Keywords: Sørishavet; havis; hydrografi; klimaendringer; marin biologi; oseanografi; polarområdene; sjøelefanter; sjøis; sjøpattedyr

Regeneration of Fe(II) during EIFeX and SOFeX - Croot, Peter L.; Bluhm, Kathrin; Schlosser, Christian; Streu, Peter; Breitbarth, Eike; Frew, Russell D.; Ardelan, Murat van (Geophysical Research Letters, 2008)
Investigations into Fe(II) cycling during two Southern Ocean mesoscale iron enrichment experiments, SOFeX and EIFeX, clearly show the importance of Fe(II) to iron speciation during these experiments. In both cases the added Fe(II) persisted significantly longer than its expected oxidation time indicating a significant Fe reduction process at work. During EIFeX diel studies showed a strong photochemically induced cycle in Fe(II) production in sunlit surface waters. Our results suggest that the photochemical cycling of iron may also be important in unfertilized waters of the Southern Ocean.
Keywords: Sørishavet; biogeokjemi; fytoplankton; marin biologi; polarområdene

From the editor: halfway through the IPY—halfway for an Antarctic traverse - Goldman, Helle V (Polar Research, 2008)
April is here and we have just passed the midpoint of the International Polar Year (IPY), which began on 1 March 2007 and will conclude on 1 March 2009. The “year” stretches over 24 months to accommodate two summer field seasons in both polar regions. The northern summer is fast approaching, and scientists who will undertake a second IPY summer season in the Arctic are making their final preparations. At the opposite end of the planet, summer is over and scientists have wrapped up the first IPY field season. Those whose projects will carry on for a second summer season will have to wait until late this year to resume work in Antarctica.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Norway and past International Polar Years—a historical account - Bones, Stian (Polar Research, 2007)
Surveying Norway’s role in past International Polar Years (IPYs), this essay by historian Stian Bones contributes to a broader understanding of Norway as a “polar nation”. He describes the strengths of Norway’s scientific traditions in the polar regions, and examines the varying motivations driving Norwegian involvement in the first three IPYs: 1882–83, 1932–33 and 1957–58 (also known as the International Geophysical Year).
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; historie; polarområdene; vitenskap

Reproductive performance and organochlorine pollutants in an Antarctic marine top predator: The south polar skua - Bustnes, Jan O; Tveraa, Torkild; Varpe, Øystein; Henden, John A; Skaare, Janneche U (Environment International, 2007)
Keywords: Dronning Maud Land; forurensning; miljø; ornitologi; polarområdene; reproduksjon; økologi

Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Organochlorines in Antarctic and Arctic Avian Top Predators: A Comparison between the South Polar Skua and Two Species of Northern Hemisphere Gulls - Bustnes, Jan O; Tveraa, Torkild; Henden, John A; Varpe, Øystein; Janssen, Kirstin; Skaare, Janneche U (Environmental Science & Technology, 2006)
Different organochlorine compounds (OCs) were measured in the blood of breeding south polar skuas (Catharacta maccormicki) at Svarthamaren, Dronning Maud Land (Antarctica) and compared to those in two species of northern hemisphere gulls:  the Arctic glaucous gull (Larus hyperboreus) and the subarctic great black-backed gull (Larus marinus). The skuas had 8% and 29% of the ∑OC levels (45 ng/g, wet weight) of glaucous gulls (591 ng/g) and great black-backed gulls (158 ng/g), respectively. Polychlorinated biphenyls (PCBs) and p,p‘-dichlorodiphenyldichloroethylene (p,p‘-DDE) were very low in skuas compared to northern gulls, but the mean hexachlorobenzene (HCB) level was 1.7 times higher than in great black-backed gulls and one-third of the glaucous gull level. Mirex levels in skuas were among the highest reported in birds, the mean level being 3 and 26 times higher than those in glaucous gull and great black-backed gulls, respectively. In skuas, the mean levels of HCB, oxychlordane, p,p‘-DDE, and PCBs increased by about 30% during a 2-week period, and mirex increased by nearly 60%. In glacuous gulls, HCB, p,p‘-DDE, and PCBs increased by 10−20%. For HCB, mirex, and oxychlordane, only a relatively small proportion of the increase in skuas could be explained by changes in lipid pools and the levels at first sampling, compared to glaucous gulls. Thus, skuas were probably accumulating these compounds when present in Antarctica. p,p‘-DDE and PCB levels, in contrast, seemed much more stable in the skuas. Relatively high levels of mirex and HCB in south polar skuas are concerning with regard to potential adverse effects.
Keywords: Dronning Maud Land; kjemiske analyser; ornitologi; polarområdene; sjøfugler

“Deckchair Explorers”: The Origin and Development of Organised Tourist Voyages to Northern and Southern Polar Regions - Kolltveit, Bård (International Journal of Maritime History, 2006)
Keywords: Antarktis; ekspedisjoner; historie; miljø; næringslivet; polarområdene; turisme

Remembering Tore Gjelsvik (1916–2006) - Orheim, Olav (Polar Research, 2006)
Tore Gjelsvik, former director of the Norwegian Polar Institute, died at the beginning of this year. He is fondly remembered by a great many people. In this piece, Olav Orheim recalls the man and his key role in Norwegian polar activities. Orheim was head of Antarctic Research at the Norwegian Polar Institute in 1972–1993 and was the institute’s director from 1993 to 2005.
Keywords: Antarktis; Norsk Polarinstitutt; biografi; geologi; polarområdene

Ozone profiles in the high-latitude stratosphere and lower mesosphere measured by the Improved Limb Atmospheric Spectrometer (ILAS)-II: Comparison with other satellite sensors and ozonesondes - Sugita, Takafumi; Nakajima, Hideaki; Yokota, T; Kanzawa, Hiroshi; Gernandt, Hartwig; Herber, A; von der Gathen, P; König-Langlo, Gert; Sato, Kaoru; Dorokhov, Valery; Yushkov, V A; Murayama, Yasuhiro; et al. (Journal of Geophysical Research: Atmospheres, 2006)
A solar occultation sensor, the Improved Limb Atmospheric Spectrometer (ILAS)-II, measured 5890 vertical profiles of ozone concentrations in the stratosphere and lower mesosphere and of other species from January to October 2003. The measurement latitude coverage was 54–71°N and 64–88°S, which is similar to the coverage of ILAS (November 1996 to June 1997). One purpose of the ILAS-II measurements was to continue such high-latitude measurements of ozone and its related chemical species in order to help accurately determine their trends. The present paper assesses the quality of ozone data in the version 1.4 retrieval algorithm, through comparisons with results obtained from comprehensive ozonesonde measurements and four satellite-borne solar occultation sensors. In the Northern Hemisphere (NH), the ILAS-II ozone data agree with the other data within ±10% (in terms of the absolute difference divided by its mean value) at altitudes between 11 and 40 km, with the median coincident ILAS-II profiles being systematically up to 10% higher below 20 km and up to 10% lower between 21 and 40 km after screening possible suspicious retrievals. Above 41 km, the negative bias between the NH ILAS-II ozone data and the other data increases with increasing altitude and reaches 30% at 61–65 km. In the Southern Hemisphere, the ILAS-II ozone data agree with the other data within ±10% in the altitude range of 11–60 km, with the median coincident profiles being on average up to 10% higher below 20 km and up to 10% lower above 20 km. Considering the accuracy of the other data used for this comparative study, the version 1.4 ozone data are suitably used for quantitative analyses in the high-latitude stratosphere in both the Northern and Southern Hemisphere and in the lower mesosphere in the Southern Hemisphere.
Keywords: Antarktis; klimatologi; meteorologi; ozonlaget; polarområdene; stratosfæren

Bipolar patterns of intraspecific competition in bryozoans - Barnes, David K A; Kuklinski, Piotr (Marine Ecology Progress Series, 2005)
Polar shores probably represent the most dynamic and extremely disturbed environments on the globe. Nevertheless intense battles amongst sessile organisms for space are commonplace on hard substrata, mainly between fast-growing pioneer species. In this study we examined spatial interactions in encrusting species at 3 sites within each of 2 high Arctic localities, Horsundfjord (77°N) and Kongsfjord (79°N) in Spitsbergen, and 2 Antarctic localities, Signy Island (60°S) and Adelaide Island (68°S). In both polar regions 1 to 11% of encrusting fauna were involved in intraspecific interactions. Intraspecific competition was common; it usually involved just 1 or 2 pioneer species, mainly ended in tied outcomes, and most variability was at a local scale. The proportion of intraspecific encounters varied considerably at local (km) scales (19 to 99% intraspecific at different sites), reflecting an extremely patchy environment due to ice scour. Most intraspecific encounters resulted in ties (stand-offs) and again most variability was at a local scale. Many intraspecific encounters were constructive, forming large (>1 m3) foliaceous colonies (termed bioconstructions) whose 3D structures can harbour rich biotas. In other colonies intraspecific competition caused crowding and accelerated ovicell production (reproductive activity). Homosyndrome (fusion) was not observed in the Arctic and was rare in the Antarctic, where its frequency differed significantly between competitor identities. We found that the likelihood of meeting conspecifics versus other species and of tied outcomes in encounters was related to the performance of species in interspecific competition: ties were most common, and homosyndrome only occurred in poor competitors. In the context of rapid Arctic and west Antarctic warming and ice-loading of nearshore waters, we predict strongly changing patterns of intraspecific competition. Indeed we suggest that decreased patchiness of intra- versus interspecific competition and decreased levels of intraspecific competition should be strong indicators of increases in surface water ice-loading from ice-sheet collapses. KEYWORDS: Sublittoral · Benthos · Bioconstruction · Climate change · Homosyndrome
Keywords: Sørishavet; bentiske organismer; bryozoa; klimaendringer; marin biologi; miljøendringer; oseanografi; polarområdene

Cryosphere-hydrosphere interactions: Numerical modeling using the regional ocean Modeling System (ROMS) at different scales - Bergamasco, Andrea; Budgell, W. P.; Carniel, Sandro; Sclavo, Mauro (Il Nuovo cimento della Società Italiana di Fisica. C. Geophysics and space physics, 2005)
Conveyor belt circulation controls global climate through heat and water fluxes with atmosphere and from tropical to polar regions and vice versa. This circulation, commonly referred to as thermohaline circulation (THC), seems to have millennium time scale and nowadays-a non-glacial period-appears to be as rather stable. However, concern is raised by the buildup Of CO2 and other greenhouse gases in the atmosphere (IPCC, Third assessment report: Climate Change 2001, A contribution of working group I, II and III to the Third Assessment Report of the Intergovernmental Panel on Climate Change (Cambridge Univ. Press, UK) 2001, http://www.ipcc.ch) as these may affect the THC conveyor paths. Since it is widely recognized that dense-water formation sites act as primary sources in strengthening quasi-stable THC paths (Stommel H., Tellus, 13 (1961) 224), in order to simulate properly the consequences of such scenarios a better understanding of these oceanic processes is needed. To successfully model these processes, air-sea-ice-integrated modelling approaches are often required. Here we focus on two polar regions using the Regional Ocean Modeling System (ROMS). In the first region investigated, the North Atlantic-Arctic, where open-ocean deep convection and open-sea ice formation and dispersion under the intense air-sea interactions are the major engines, we use a new version of the coupled hydrodynamic-ice ROMS model. The second area belongs to the Antarctica region inside the Southern Ocean, where brine rejections during ice formation inside shelf seas origin dense water that, flowing along the continental slope, overflow becoming eventually abyssal waters. Results show how nowadays integrated-modelling tasks have become more and more feasible and effective; numerical simulations dealing with large computational domains or challenging different climate scenarios can be run on multi-processors platforms and on systems like LINUX clusters, made of the same hardware as PCs, and codes have been accordingly modified. This relevant numerical help coming from the computer science can now allow scientists to devote larger attention in the efforts of understanding the deep mechanisms of such complex processes.
Keywords: Sørishavet; geofysikk; klimaendringer; klimamodeller; oseanografi; polarområdene

Polar bivalves are characterized by high antioxidant defences - Camus, Lionel; Gulliksen, Bjørn; Depledge, Michael H; Jones, Malcolm B (Polar Research, 2005)
Inevitably, aerobic life leads to the formation of deleterious reactive oxygen species (ROS) which participate in biomolecule oxidation, hence augmenting biomolecule turnover. Organisms have adapted to counteract the noxious effects of ROS by developing a battery of antioxidant defences (AOX) which comprise enzymes and low-molecular weight scavengers. Past studies have reported elevated AOX levels in polar pectinid bivalves compared with temperate congeners. This fi nding is controversial as mitochondrial ROS generation is low in polar versus temperate species, and, to date, there is no generally accepted explanation of the causes of increased basal AOX levels in polar waters. We suggest that the low food availability in those ecosystems may result in polar marine ectotherms diverting some energy into the maintenance of high AOX. We tested this hypothesis by comparing the total oxyradical scavenging capacity (peroxyl, hydroxyl and peroxynitrite) of three clam species: Laternula elliptica (Antarctic), Mya truncata (Arctic) and Mya arenaria (temperate). The data confi rmed that polar bivalves are characterized by higher AOX. Herein, we propose that high AOX is required in environments characterized by low food availability as AOX effi ciently protects biomolecules, notably the RNA expressed at high levels by cold-water ectotherms. Also, high AOX may explain the relatively long lifespan of most polar ectotherms.
Keywords: Sørishavet; marin biologi; muslinger; polarområdene

Modeling the middle Pliocene climate with a global atmospheric general circulation model - Jiang, Dabang; Wang, Huijun; Ding, Zhongli; Lang, Xianmei; Drange, Helge (Journal of Geophysical Research: Atmospheres, 2005)
A new climate simulation for the middle Pliocene (ca. 3 Ma BP) is performed by a global grid-point atmospheric general circulation model developed at the Institute of Atmospheric Physics (IAP AGCM) with boundary conditions provided by the U. S. Geological Survey's Pliocene Research, Interpretations, and Synoptic Mapping (PRISM) group. It follows that warmer and slightly wetter conditions dominated at the middle Pliocene with a globally annual mean surface temperature increase of 2.60°C, and an increase in precipitation of 4.0% relative to today. At the middle Pliocene, globally annual terrestrial warming was 1.86°C, with stronger warming toward high latitudes. Annual precipitation enhanced notably at high latitudes, with the augment reaching 33.5% (32.5%) of the present value at 60–90°N (60–90°S). On the contrary, drier conditions were registered over most parts at 0–30°N, especially in much of East Asia and the northern tropical Pacific. In addition, both boreal summer and winter monsoon significantly decreased in East Asia at the middle Pliocene. It is indicated that the IAP AGCM simulation is generally consistent with the results from other atmospheric models and agrees well with available paleoclimatic reconstructions in East Asia. Additionally, it is further revealed that the PRISM warmer sea surface temperature and reduced sea ice extent are main factors determining the middle Pliocene climate. The simulated climatic responses arising from the PRISM reconstructed vegetation and continental ice sheet cannot be neglected on a regional scale at mid to high latitudes (like over Greenland and the Qinghai-Tibetan Plateau, and around the circum-Antarctic) but have little influence on global climate.
Keywords: Antarktis; global klimamodell; global oppvarming; innlandsis; paleoklimatologi; polarområdene

Belgica in the Arctic - Kjær, Kjell-G. (Polar Record, 2005)
Belgica, which Adrien de Gerlache used on the first expedition to winter in the Antarctic, was originally a bottlenose whaler named Patria, built in Norway in 1884. She was designed and constructed by Johan Chr. Jakobsen, renowned for his design of polar ships. Patria was sold to Adrien de Gerlache and renamed Belgica in 1896. In 1896–97 she was refitted and equipped in Sandefjord, Norway, for an Antarctic expedition. Nansen and Amundsen met for the first time on Belgica's deck. Late in 1899 Belgica returned to Antwerp after more than two years on an Antarctic expedition. From 1901 to 1904 Belgica returned to bottlenose whaling and, in addition, made a voyage to northeast Greenland to establish depots and build houses for the Baldwin-Ziegler Polar Expedition. In 1905 the Duc d'Orléans chartered her to survey the coast of northeast Greenland, and on her return he bought her. In 1907 and 1909 she sailed on Arctic expeditions led by the Duc d'Orléans and captained by de Gerlache. In 1916 she was sold to Det Norske Kulsyndikat and renamed Isfjord. She became a freighter carrying coal from Longyearbyen to ports in northern Norway. In 1918 she was sold and her new owner converted her into a floating cod-liver oil refinery and fish-processing plant. In 1940 she was impounded by British forces and used as a floating ammunition depot. On 19 May 1940 she was sunk during a German air raid. Her wreck was re-discovered in 1990.
Keywords: Antarktis; Belgica (skip); Belgica ekspedisjon; Roald Amundsen; overvintring; polarekspedisjoner; polarområdene

Pole-to-pole validation of Envisat GOMOS ozone profiles using data from ground-based and balloon sonde measurements - Meijer, Yasjka; Swart, Daan P J; Allaart, M; Andersen, S B; Bodeker, G; Boyd, I; Braathen, Geir; Calisesi, Yasmine; Claude, H; Dorokhov, Valery; von der Gathen, P; Gil, M; et al. (Journal of Geophysical Research: Atmospheres, 2004)
In March 2002 the European Space Agency (ESA) launched the polar-orbiting environmental satellite Envisat. One of its nine instruments is the Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument, which is a medium-resolution stellar occultation spectrometer measuring vertical profiles of ozone. In the first year after launch a large group of scientists performed additional measurements and validation activities to assess the quality of Envisat observations. In this paper, we present validation results of GOMOS ozone profiles from comparisons to microwave radiometer, balloon ozonesonde, and lidar measurements worldwide. Thirty-one instruments/launch sites at twenty-five stations ranging from the Arctic to the Antarctic joined in this activity. We identified 6747 collocated observations that were performed within an 800-km radius and a maximum 20-hour time difference of a satellite observation, for the period between 1 July 2002 and 1 April 2003. The GOMOS data analyzed here have been generated with a prototype processor that corresponds to version 4.02 of the operational GOMOS processor. The GOMOS data initially contained many obviously unrealistic values, most of which were successfully removed by imposing data quality criteria. Analyzing the effect of these criteria indicated, among other things, that for some specific stars, only less than 10% of their occultations yield an acceptable profile. The total number of useful collocated observations was reduced to 2502 because of GOMOS data unavailability, the imposed data quality criteria, and lack of altitude overlap. These collocated profiles were compared, and the results were analyzed for possible dependencies on several geophysical (e.g., latitude) and GOMOS observational (e.g., star characteristics) parameters. We find that GOMOS data quality is strongly dependent on the illumination of the limb through which the star is observed. Data measured under bright limb conditions, and to a certain extent also in twilight limb, should be used with caution, as their usability is doubtful. In dark limb the GOMOS data agree very well with the correlative data, and between 14- and 64-km altitude their differences only show a small (2.5–7.5%) insignificant negative bias with a standard deviation of 11–16% (19–63 km). This conclusion was demonstrated to be independent of the star temperature and magnitude and the latitudinal region of the GOMOS observation, with the exception of a slightly larger bias in the polar regions at altitudes between 35 and 45 km.
Keywords: Antarktis; fjernmåling; meteorologi; målinger; ozonlaget; polarområdene; stratosfæren

The diatom Fragilariopsis cylindrus and its potential as an indicator species for cold water rather than for sea ice - Quillfeldt von, Cecilie Hellum (Vie et Milieu / Life & Environment, 2004)
The importance of the diatom Fragilariopsis cylindrus (Grunow) Krieger in Helmcke & Krieger in the Arctic and Antarctic is well known. It is used as an indicator of sea ice when the paleoenvironment is being described. It is often among the dominant taxa in different sea ice communities, sometimes making an important contribution to a subsequent phytoplankton growth when released by ice melt. However, it may also dominate phytoplankton blooms in areas never experiencing sea ice. The use of F. cylindrus as an indicator for reconstruction of palaeoceanographic conditions is assessed from literature records. Its potential as an indicator species for sea ice appears to vary from region to region, but it is a good indicator of cold water.
Keywords: Sørishavet; diatomeer; marin biologi; paleoseanografi; phytoplankton; polarområdene

Some features of electron density behaviour in the high latitude D-region derived from in situ measurements - Danilov, A.D.; Smirnova, N.V.; Blix, Tom Arild; Thrane, E.V.; Vanina, L.B. (Journal of Atmospheric and Solar-Terrestrial Physics, 2003)
A large database of rocket measurements of the D-region electron concentration has been studied. The data were obtained at four sites in the Antarctic (Molodezhnaya and Syowa) and Arctic (Heiss Island, and Andøya/Kiruna). The electron densities were analysed in terms of their variations with solar zenith angle, geomagnetic activity and atmospheric temperature. We found that there is a particle ionisation source in the auroral oval even in quiet conditions. The energy of the particles is such, that they penetrate down to 85km, are partially absorbed between 85 and 80km but do not penetrate (are completely absorbed) below 75km. Analysis of the dependence of the electron concentration [e] on the daily sum of Kp indices, ∑Kp, shows that at all heights considered there is an increase of [e] with ∑Kp up to some saturation value of ∑Kp and beyond this level [e] is either constant (with large scatter of the data) or even decreases. This indicates that when the auroral oval expands with increasing geomagnetic activity, a particular station may move from a position outside or at the boundary of the oval, to a position inside the polar cap. An attempt is made to find the temperature dependence of the electron concentration. It is found that [e] at 75 and 80km increases with temperature T. Analysis of the flights conducted during noctilucent cloud (NLC) events at Andøya/Kiruna reveals a strong dependence of [e] on ∑Kp at 80 and 85km. This dependence is stronger and better defined than that for the entire data set. This may be explained by the low mesopause temperatures observed in summer when NLC occur. A comparison of the electron density data sets with empirical and theoretical models is presented and during quiet magnetic conditions a good agreement with mid-latitude models is found.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Sea ice extent and the global climate system - Dick, Chad (Polar Research, 2003)
Sea ice is a remarkable component of the global climate system. It can form over up to about 10 % of the global ocean area, and creates an insulating barrier between the relatively warm seawater and the cold atmosphere, allowing a temperature difference that may be tens of degrees over only a couple of meters. It reduces evaporation from the ocean, leading to a drier atmosphere than would otherwise exist. Sea ice modifies the radiation balance at the Earth’s surface because it supports snow (the most reflective of the Earth’s natural surfaces, with an albedo of up to approximately 0.8), where otherwise there would be seawater (the least reflective, with an albedo of about 0.07). As sea ice forms it excludes brine, deepening the ocean surface mixed layer and influencing the formation of deep and bottom water. As it melts, it releases relatively fresh water, stratifying the upper layers of the ocean. Through these processes sea ice exerts an enormous influence on the atmospheric and oceanic circulation in cold regions and indeed the climate of the rest of the globe.
Keywords: Sørishavet; globale klimasystemet; havis; klimaendringer; polarområdene; sjøis

A hindcast simulation of Arctic and Antarctic sea ice variability, 1955-2001 - Fichefet, Thierry; Goosse, Hugues; Morales Maqueda, Miguel Angel (Polar Research, 2003)
A hindcast simulation of the Arctic and Antarctic sea ice variability during 1955–2001 has been performed with a global, coarse resolution ice–ocean model driven by the National Centers for Environmental Prediction / National Center for Atmospheric Research reanalysis daily surface air temperatures and winds. Both the mean state and variability of the ice packs over the satellite observing period are reasonably well reproduced by the model. Over the 47-year period, the simulated ice area (defined as the total ice-covered oceanic area) in each hemisphere experiences large decadal variability together with a decreasing trend of ~1 % per decade. In the Southern Hemisphere, this trend is mostly caused by an abrupt retreat of the ice cover during the second half of the 1970s and the beginning of the 1980s. The modelled ice volume also exhibits pronounced decadal variability, especially in the Northern Hemisphere. Besides these fluctuations, we detected a downward trend in Arctic ice volume of 1.8 % per decade and an upward trend in Antarctic ice volume of 1.5 % per decade. However, caution must be exercised when interpreting these trends because of the shortness of the simulation and the strong decadal variations. Furthermore, sensitivity experiments have revealed that the trend in Antarctic ice volume is model-dependent.
Keywords: Sørishavet; forskning; geofysikk; havis; observasjoner; polarområdene; satellitt; sjøis

Description and evaluation of the bergen climate model: ARPEGE coupled with MICOM - Furevik, Tore; Bentsen, Mats; Drange, Helge; Kindem, I. K. T.; Kvamstø, Nils Gunnar; Sorteberg, Asgeir (Climate Dynamics, 2003)
A new coupled atmosphere–ocean–sea ice model has been developed, named the Bergen Climate Model (BCM). It consists of the atmospheric model ARPEGE/IFS, together with a global version of the ocean model MICOM including a dynamic–thermodynamic sea ice model. The coupling between the two models uses the OASIS software package. The new model concept is described, and results from a 300-year control integration is evaluated against observational data. In BCM, both the atmosphere and the ocean components use grids which can be irregular and have non-matching coastlines. Much effort has been put into the development of optimal interpolation schemes between the models, in particular the non-trivial problem of flux conservation in the coastal areas. A flux adjustment technique has been applied to the heat and fresh-water fluxes. There is, however, a weak drift in global mean sea-surface temperature (SST) and sea-surface salinity (SSS) of respectively 0.1 °C and 0.02 psu per century. The model gives a realistic simulation of the radiation balance at the top-of-the-atmosphere, and the net surface fluxes of longwave, shortwave, and turbulent heat fluxes are within observed values. Both global and total zonal means of cloud cover and precipitation are fairly close to observations, and errors are mainly related to the strength and positioning of the Hadley cell. The mean sea-level pressure (SLP) is well simulated, and both the mean state and the interannual standard deviation show realistic features. The SST field is several degrees too cold in the equatorial upwelling area in the Pacific, and about 1 °C too warm along the eastern margins of the oceans, and in the polar regions. The deviation from Levitus salinity is typically 0.1 psu – 0.4 psu, with a tendency for positive anomalies in the Northern Hemisphere, and negative in the Southern Hemisphere. The sea-ice distribution is realistic, but with too thin ice in the Arctic Ocean and too small ice coverage in the Southern Ocean. These model deficiencies have a strong influence on the surface air temperatures in these regions. Horizontal oceanic mass transports are in the lower range of those observed. The strength of the meridional overturning in the Atlantic is 18 Sv. An analysis of the large-scale variability in the model climate reveals realistic El Niño – Southern Oscillation (ENSO) and North Atlantic–Arctic Oscillation (NAO/AO) characteristics in the SLP and surface temperatures, including spatial patterns, frequencies, and strength. While the NAO/AO spectrum is white in SLP and red in temperature, the ENSO spectrum shows an energy maximum near 3 years.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; polarområdene

Calcareous dinoflagellate associations and Maastrichtian–Tertiary climatic change in a high-latitude core (ODP Hole 689B, Maud Rise, Weddell Sea) - Hildebrand-Habel, Tania; Streng, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
The distribution of calcareous dinoflagellates has been analysed for the Maastrichtian–Miocene interval of Ocean Drilling Project Hole 689B (Maud Rise, Weddell Sea). The investigation thus represents a primary evaluation of the long-term evolution in high-latitude calcareous dinoflagellate assemblages during the transition from a relatively warm Late Cretaceous to a cold Neogene climate. Major assemblage changes during this interval occurred in characteristic steps: (1) an increase in relative abundance of tangentially structured species – particularly Operculodinella operculata – at the Cretaceous/Tertiary boundary; (2) a diversity decrease and several first and last appearances across the Middle–Late Eocene boundary, possibly attributed to increased climate cooling; (3) a diversity decrease associated with the dominance of Calciodinellum levantinum in the late Early Oligocene; (4) the reappearance and dominance of Pirumella edgarii in the Early Miocene, probably reflecting a warming trend; (5) monogeneric assemblages dominated by Caracomia spp. denoting strong Middle Miocene cooling. The results not only extend the biogeographic ranges of many taxa into the Antarctic region, but also indicate that the evolution of high-latitude calcareous dinoflagellate assemblages parallels the changing environmental conditions in the course of the Cenozoic climate transition. Therefore, calcareous dinoflagellates contribute to our understanding of the biotic effects associated with palaeoenvironmental changes and might possess the potential for reconstructing past conditions. The flora in the core includes one new taxon: Caracomia arctica forma spinosa Hildebrand-Habel and Streng, forma nov. Additionally, two new combinations are proposed: Fuettererella deflandrei (Kamptner, 1956) Hildebrand-Habel and Streng, comb. nov. and Fuettererella flora (Fütterer, 1990) Hildebrand-Habel and Streng, comb. nov.
Keywords: Sørishavet; Weddellhavet; geologi; klimaendringer; paleogeografi; paleoklimatologi; polarområdene

Women and couples in isolated extreme environments: applications for long-duration missions - Leon, Gloria R.; Sandal, Gro Mjeldheim (Acta Astronaut, 2003)
Expedition teams provide a number of analogs relevant to crew selection for long-duration space missions. Three groups were studied that varied in team composition. Group 1 was a two woman international dyad that traversed the Antarctic continent in 97 days. Similarities in problem solving approach, respect for each other's opinions, and a collaborative process of decision making were evident. Group 2 was composed of four women, all from different countries, engaged in a six week trek across Greenland. The most important factors in overcoming interpersonal difficulties and contributing to the successful completion of the expedition were mutual respect and motivation to maintain positive and supportive relationships. Group 3 consisted of three married couples from different countries icelocked on a boat in the High Arctic for a 9 month period. The emotional support of and ability to confide in their partner were extremely important in alleviating interpersonal tensions, and contributed to the generally effective functioning of the group. Women add an element of emotional support and help to other team members that is not as evident in all-male groups. Selection of couples with strong bonds to each other is another paradigm for crew selection for extended missions.
Keywords: Antarktis; polareksspedisjoner; polarforskere; polarområdene; psykologi

Sea ice formation on a very cold surface - Smedsrud, Lars Henrik; Saloranta, Tuomo; Haugan, Peter M; Kangas, Tor-Villy (Geophysical Research Letters, 2003)
In this study laboratory experiments of sea ice formed on a vertical surface with initial temperature of −30 to −50°C are presented. The ice formation is rapid, and in 300 s >5 mm of sea ice is formed. Ice formation cooled and salinified the water, and induced a vertical down wards flow of ∼5 mm/s with a boundary layer about 5 mm thick. This ice has a structure with columnar crystals that have small circular cross sections (0.2–1.0 mm) and sea ice salinities are between 24 and 32. A simple model approach indicate that the thermal conductivity of such ice is lower than for other types of sea ice.
Keywords: Antarktis; geofysikk; glasiologi; havis; innlandsis; isshelf; laboratorieeksperimenter; polarområdene; sjøis

Species richness of marine soft sediments - John, S Gray (Marine Ecology Progress Series, 2002)
Marine soft sediments comprise one of the largest and oldest habitats in the world, yet remarkably little is known about patterns of species richness. Here I present a short review of patterns of species richness and possible factors that influence such patterns. Species richness in general is remarkably high in both shallow coastal areas and the deep sea. However, there are clear differences the deep-sea has higher number of species for a given number of individuals than the coast. This can be explained by the larger amounts of primary production that reach coastal compared with deep-sea sediments, leading to higher numbers of individuals per unit area. Species density (the number of species per unit area) is also higher in the deep-sea than in coastal areas, but it is not obvious why this is so. Most studies of the broad patterns of species richness have used samples taken at small scales only. The problem with such analyses is that unless a large number of samples are taken, the true underlying pattern (or lack of it) may be wrongly interpreted. Recent studies have analysed species richness at larger scales. In general there seems to be a cline of increasing species richness from the Arctic to the tropics, but this is not the case in the southern hemisphere, where Antarctic species richness is high. However, it is not known whether high species richness in the Antarctic occurs at all spatial scales. To what extent these patterns are determined by evolutionary factors remains to be determined by the application of molecular methods. The available evidence suggests that environmental factors such as productivity, temperature, and sediment grain-size diversity play dominant roles in determining patterns of regional-scale species richness and patterns in species turnover, and it is probably the regional scale that primarily determines local species richness. KEYWORDS: Diversity · Deep sea · Coasts · Patterns · Scales
Keywords: Sørishavet; biodiversitet; marin biologi; polarområdene

Comparison of measurements and model calculations of stratospheric bromine monoxide - Sinnhuber, Björn‐Martin; Arlander, D William; Bovensmann, H; Burrows, J P; Chipperfield, M P; Enell, Carl-Fredrick; Frieß, U; Hendrick, F; Johnston, P V; Jones, R L; Kreher, K; Mohamed-Tahrin, N; et al. (Journal of Geophysical Research: Atmospheres, 2002)
Ground-based zenith sky UV–visible measurements of stratospheric bromine monoxide (BrO) slant column densities are compared with simulations from the SLIMCAT three-dimensional chemical transport model. The observations have been obtained from a network of 11 sites, covering high and midlatitudes of both hemispheres. This data set gives for the first time a near-global picture of the distribution of stratospheric BrO from ground-based observations and is used to test our current understanding of stratospheric bromine chemistry. In order to allow a direct comparison between observations and model calculations, a radiative transfer model has been coupled to the chemical model to calculate simulated slant column densities. The model reproduces the observations in general very well. The absolute amount of the BrO slant columns is consistent with a total stratospheric bromine loading of 20 ± 4 ppt for the period 1998–2000, in agreement with previous estimates. The seasonal and latitudinal variations of BrO are well reproduced by the model. In particular, the good agreement between the observed and modeled diurnal variation provides strong evidence that the BrO-related bromine chemistry is correctly modeled. A discrepancy between observed and modeled BrO at high latitudes during events of chlorine activation can be resolved by increasing the rate constant for the reaction BrO + ClO → BrCl + O2 to the upper limit of current recommendations. However, other possible causes of the discrepancy at high latitudes cannot be ruled out.
Keywords: Antarktis; atmosfæren; fysikk; kjemiske analyser; meteorologi; miljø; målinger; polarområdene; stratosfæren

Norwegian use of the polar oceans as occupational arenas and exploration routes - Barr, Susan (Polar Record, 2001)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; forskning; geografi; historie; oppdagelsesreiser; polarområdene

Electron density variations in the upper D region at high latitudes according to in situ measurements - Danilov, Alexey; Smirnova, N.V.; Vanina-Dart, Liudmila; Blix, Tom Arild; Thrane, Eivind (Geomagnetism and Aeronomy, 2001)
A large set of rocket measurements of the electron concentration [e] in the upper D region at four rocket sites (Molodezhnaya (Antarctic), Heiss Island (Arctic), Syowa (Antarctic), and Andoya/Kiruna (Arctic)) is considered. The dependence of [e] on the solar zenith angle X and geomagnetic activity index ∑Kp is analyzed. It has been shown that, the spread in [e] values reaches two orders of magnitude at any assigned value of χ. Nevertheless, it is possible to draw a lower envelope for the entire set of points and to obtain the [e] variation with χ in undisturbed conditions. In an analysis of the envelopes, it is seen that a corpuscular ionization source (presumably, electrons with an energy of above 40 keV) exists in the nonsunlit D region even in quiet conditions. An analysis of the electron concentration dependence on the daily sum of ∑Kp indices (∑Kp) shows that, at all heights considered, increases [e] with increasing ∑Kp to a certain boundary value ∑Kp and then remains either constant (with a rather wide spread in the data) or even decreases. This saturation effect may be caused by the auroral oval equatorward motion. As a result of this motion the site position may change: it may move toward the boundary between the auroral oval and polar cap or even be within the latter. The slope k of the [e] variation plotted versus ∑Kp at different χ is considered. It is shown that k grows with increasing χ and is maximal at χ> 100°.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Man in extreme environments - Brubakk, Alf O. (Aviation, space, and environmental medicine, 2000)
Humans have demonstrated the ability to live and work in many adverse environments. Many examples demonstrate that our understanding of humans ability to adapt to extreme environments is limited, but it is reasonable to assume that the main problems in space exploration will be psychological and social. It is argued that polar expeditions of an earlier age are a better model for space exploration than confinement studies or Antarctic overwintering. Some aspects of the reason for the success of these expeditions are discussed and the lessons that can be used are pointed out.
Keywords: Antarktis; fysiologi; overvintring; polarekspedisjoner; polarområdene

Combined characterisation of GOME and TOMS total ozone measurements from space using ground-based observations from the NDSC - Lambert, J.-C.; Van Roozendael, M.; Simon, P.C.; Pommereau, J.-P.; Goutail, F.; Gleason, J.F.; Andersen, S.B.; Arlander, D.W.; Bui Van, N.A.; Claude, H.; de La Noë, J.; De Mazière, M.; et al. (Advances in Space Research, 2000)
Several years of total ozone measured from space by the ERS-2 GOME, the Earth Probe TOMS, and the ADEOS TOMS, are compared with high-quality ground-based observations associated with the Network for the Detection of Stratospheric Change (NDSC), over an extended latitude range and a variety of geophysical conditions. The comparisons with each spaceborne sensor are combined altogether for investigating their respective solar zenith angle (SZA) dependence, dispersion, and difference of sensitivity. The space- and ground-based data are found to agree within a few percent on average. However, the analysis highlights for both GOME and TOMS several sources of discrepancies: (i) a SZA dependence with TOMS beyond 80° SZA; (ii) a seasonal SZA dependence with GOME beyond 70° SZA; (iii) a difference of sensitivity with GOME at high latitudes; (iv) a difference of sensitivity to low ozone values between satellite and SAOZ sensors around the southern tropics; (v) a north/south difference of TOMS with the ground-based observations; and (vi) internal inconsistencies in GOME total ozone.
Keywords: Antarktis; fjernmåling; geofysikk; meteorologi; ozonlaget; polarområdene; satellitt observasjoner

Arctic and Antarctic ozone layer observations: chemical and dynamical aspects of variability and long-term changes in the polar stratosphere - Rex, Markus; Dethloff, Klaus; Handorf, Dörthe; Herber, Andreas; Lehmann, Ralph; Neuber, Roland; Notholt, Justus; Rinke, Annette; von der Gathen, Peter; Weisheimer, Antje; Gernandt, Hartwig (Polar Research, 2000)
The altitude dependent variability of ozone in the polar stratosphere is regularly observed by balloon-borne ozonesonde observations at Neumayer Station (70°S) in the Antarctic and at Koldewey Station (79°N) in the Arctic. The reasons for observed seasonal and interannual variability and long-term changes are discussed. Differences between the hemispheres are identified and discussed in light of differing dynamical and chemical conditions. Since the mid- 1980s, rapid chemical ozone loss has been recorded in the lower Antarctic stratosphere during the spring season. Using coordinated ozone soundings in some Arctic winters, similar chemical ozone loss rates have been detected related to periods of low temperatures. The currently observed cooling trend of the stratosphere, potentially caused by the increase of anthropogenic greenhouse gases, may further strengthen chemical ozone removal in the Arctic. However, the role of internal climate oscillations in observed temperature trends is still uncertain. First results of a 10000 year integration of a low order climate model indicate significant internal climate variability. on decadal time scales, that may alter the effect of increasing levels of greenhouse gases in the polar stratosphere.
Keywords: Antarktis; drivhusgasser; klimaendringer; klimagasser; meteorologi; observasjoner; ozonlaget; polarområdene; stratosfæren

Coping in Antarctica: is it possible to generalize results across settings? - Sandal, Gro Mjeldheim (Aviation Space and Environmental Medicine, 2000)
Background: To gain knowledge about psychological issues in space, data have been collected from groups in isolated and confined settings on Earth. This study examines the possibility of generalizing psychological findings across such environments. HYPOTHESIS: Psychological reactions among personnel in different Antarctic environments show similar time patterns. Antarctic personnel differ in personality from submariners to crews confined in hyperbaric chambers to military recruits. METHOD: Psychological reactions were evaluated by the Revised Antarctic Questionnaire. The Personality Characteristic Inventory was used to measure personality. RESULTS: Personnel stationed on a ship (n = 19) showed high coping during the whole mission, whereas personnel on land bases (n = 18) showed a marked decline around the third quarter. Reduced coping in the land-based groups was associated with stress from interpersonal relationships. Compared with submariners (n = 54) and hyperbaric chamber crews (n = 20), Antarctic personnel scored lower on competitiveness and higher on achievement striving. CONCLUSIONS: Similarities in physical, individual and group characteristics should be considered before extrapolating psychological findings across settings.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

The impact of greenhouse gases and halogenated species on future solar UV radiation doses - Taalas, Petteri; Kaurola, Jussi; Kylling, Arve; Shindell, Drew; Sausen, Robert; Dameris, Martin; Grewe, Volker; Herman, Jay; Damski, Juhani; Steil, Benedikt (Geophysical Research Letters, 2000)
The future development of stratospheric ozone layer depends on the concentration of chlorine and bromine containing species. The stratosphere is also expected to be affected by future enhanced concentrations of greenhouse gases. These result in a cooling of the winter polar stratosphere and to more stable polar vortices which leads to enhanced chemical depletion and reduced transport of ozone into high latitudes. One of the driving forces behind the interest in stratospheric ozone is the impact of ozone on solar UV-B radiation. In this study UV scenarios have been constructed based on ozone predictions from the chemistry-climate model runs carried out by GISS, UKMO and DLR. Since cloudiness, albedo and terrain height are also important factors, climatological values of these quantities are taken into account in the UV calculations. Relative to 1979–92 conditions, for the 2010–2020 time period the GISS model results indicate a springtime enhancement of erythemal UV doses of up to 90% in the 60–90 °N region and an enhancement of 100% in the 60–90 °S region. The corresponding maximum increases in the annual Northern Hemispheric UV doses are estimated to be 14% in 2010–20, and 2% in 2040–50. In the Southern Hemisphere 40% enhancement is expected during 2010–20 and 27% during 2040–50.
Keywords: Antarktis; UV-stråling; drivhusgasser; klimaendringer; klimatologi; ozonlaget; polarområdene; ultrafiolett stråling

The importance of charged aerosols in the polar mesosphere in connection with Noctilucent Clouds and Polar Mesosphere Summer Echoes - Blix, Tom Arild (The Antarctic and Arctic Middle Atmospheres: Their Differences and Similarities, 1999)
A number of campaigns have been conducted in order to study Polar Mesosphere Summer Echos (PMSE) and Noctilucent Clouds (NLC) in the period 1991–1994. Several sounding rockets have been launched through these layers with measurements being performed on upleg as well as downleg. These include measurements of positive ions and electrons in both ram and wake positions, as well as measurements of charged aerosols in ram on upleg. In this paper we will review these measurements and make a preliminary classification of the data based upon the presence of PMSE and/or NLC. One of the mechanisms responsible for PMSE is the presence of neutral air turbulence in combination with a high Schmidt number. We will briefly discuss this type of echo using in situ rocket data. Differences and similarities of PMSE and NLC as observed both in the Arctic and the Antarctic will be discussed. Observations show that especially PMSE are much more frequent in the Arctic. This may be due to a difference in the water vapour content or the temperature at mesopause heights. Lack of data in the Antarctic makes it difficult to decide which of these two factors are the most important. More measurements, especially co-ordinated in situ and ground-based lidar and radar measurements, are needed to discuss the Arctic and Antarctic similarities and differences in further detail.
Keywords: Antarktis; astrofysikk; atmosfæren; geofysikk; mesosfæren; meteorologi; polarområdene

The cryosphere: an early indicator and global player - Grassl, Hartmut (Polar Research, 1999)
Ice at or below the surface of the planet Earth is an important part of the climate system. The solid phase of water has two unique characteristics which make it both an early indicator of climate change and a global player. First, if warmed to the melting point at 0°C, higher air temperatures and/or higher long-wave back radiation just increase the melting rate but not - as with all other surfaces- the temperature, which stays at 0°C. Small icecaps and mountain glaciers thus become early indicators of a changed climate. Second. If seawater is cooled to the freezing point at about- 1.8"C. the sea ice formation process ejects salt causing the denser water to sink, thereby filling the global ocean interior with very cold water. The location where most of this deep convection occurs is strongly dependent on the freshwater balance and thus on the average salinity of ocean basins. Present ocean configuration and ocean topography, as well as precipitation distribution, make the northern North Atlantic more saline than any other high latitude ocean part and thus the site with most of this deep water formation. Sea ice formation is therefore of high significance for the European climate. Since it drives the near surface warm North Atlantic current northward off the European coast in compensation for southward deep water flow in the western Atlantic, northwestern Europe is warmer by about 4°C than the same latitudes on the eastern Pacific coast of America.
Keywords: Antarktis; isbreer; klimaendringer; kryosfæren; polarområdene; sjøvann; vann

Predicted present-day evolution patterns of ice thickness and bedrock elevation over Greenland and Antarctica - Huybrechts, Philippe; Le Meur, Emmanuel (Polar Research, 1999)
This paper discusses predicted evolution patterns of present-day changes of ice thickness, surface elevation, and bedrock elevation over the Greenland and Antarctic continents. These were obtained from calculations with dynamic 3-D ice sheet models which were coupled to a visco-elastic solid Earth model. The experiments were initialized over the last two glacial cycles and subsequently averaged over the last 200 years to obtain the current evolution. The calculations indicate that the Antarctic Ice Sheet is still adjusting to the last glacial-interglacial transition yielding a decreasing ice volume and a rising bedrock elevation of the order of several centimetres per year. The Greenland Ice Sheet was found to be close to a stationary state with a mean thickness change of only a few millimetres per year, but the calculations revealed large spatial differences. Predicted patterns over Greenland are characterized by a small thickening over the ice sheet interior and a general thinning of the ablation area. In Antarctica, almost all of the predicted changes are concentrated in the West Antarctic Ice Sheet, which is still retreating at both the Weddell and Ross Sea margins. Over most of both ice sheets, the model indicates that the surface elevation trend is dominated by ice thickness changes rather than by bedrock elevation changes.
Keywords: Antarktis; glasiologi; innlandsis; polarområdene

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

Global change and the polar regions - Rapley, Chris (Polar Research, 1999)
Keywords: Antarktis; klimaendringer; polarområdene

A global model tool for three-dimensional multiyear stratospheric chemistry simulations: Model description and first results - Rummukainen, Markku; Isaksen, Ivar S A; Rognerud, Bjørg; Stordal, Frode (Journal of Geophysical Research: Atmospheres, 1999)
The paper presents a new global modeling tool, Stratospheric Chemical Transport Model 2. It has been developed for effective three-dimensional multiyear stratospheric chemistry studies, featuring an extensive chemistry scheme, heterogeneous processing on sulfate aerosols, and some polar stratospheric cloud processes. The transport algorithm maintains sub-grid-scale distributions and connects vertically the stratospheric layers, even in a coarse vertical grid. The model has been integrated for 49 months, recycling 1 year of precalculated transport from a middle atmosphere general circulation model. One year of daily National Centers for Environmental Prediction global analyses are used as temperatures. Diurnal cycles of photolysis rates are recalculated every 7 days to give interaction with ozone changes. The model is able to describe most of the geographical and seasonal ozone variability and the meridional distributions of ozone, reactive nitrogen, chlorine, and bromine. Stratospheric diurnal cycles for nitrogen, hydrogen, chlorine, and bromine species are captured in detail. The upper stratosphere ozone deficiency, typical to models, is large. Its sensitivity to different ways of tuning are explored. Midlatitude, rather than polar, wintertime processes have so far been the focus in this model tool. The present transport and grid resolution are not suited for realistic simulations at high latitudes. As there is only a limited inclusion of polar stratospheric cloud (PSC) microphysics, chemical processing in the cold polar lower stratosphere also cannot be well simulated. For example, the Antarctic ozone hole is not simulated, but the modeled chemistry should be suitable for warm Arctic winters when type II PSCs and particle sedimentation do not occur.
Keywords: Antarktis; geofysikk; meteorologi; ozonlaget; polarområdene; stratosfæren; stratosfærisk kjemi

Residue determinants and sequence analysis of cold-adapted trypsins - Schrøder Leiros, Hanna-Kirsti; Willassen, Nils Peder; Smalås, Arne O. (Extremophiles, 1999)
The digestive enzyme trypsin is among the most extensively studied proteins, and its structure has been reported from a large number of organisms. This article focuses on the trypsins from vertebrates adapted to life at low temperatures. Cold-adapted organisms seem to have compensated for the reduced reaction rates at low temperatures by evolving more active and less temperature-stable enzymes. We have analyzed 27 trypsin sequences from a variety of organisms to find unique attributes for the cold-adapted trypsins, comparing trypsins from salmon, Antarctic fish, cod, and pufferfish to other vertebrate trypsins. Both the "cold" and the "warm" active trypsins have about 50 amino acids that are unique and conserved within each class. The main unique features of the cold-adapted trypsins attributable to low-temperature adaptation seem to be (1) reduced hydrophobicity and packing density of the core, mainly because of a lower (Ile + Leu)/(Ile + Leu + Val) ratio, (2) reduced stability of the C-terminal, (3) lack of one warm trypsin conserved proline residue and one proline tyrosine stacking, (4) difference in charge and flexibility of loops extending the binding pocket, and (5) different conformation of the "autolysis" loop that is likely to be involved in substrate binding.
Keywords: Sørishavet; biokjemi; fisker; marin biologi; mikrobiologi; polarområdene

The interplay of global and polar regimes - Young, Oran R. (Polar Research, 1999)
The growing salience of interactions between the functionally broad but geographically narrow regimes for the polar regions and the geographically broad but functionally specific regimes emerging to deal with global environmental changes directs attention to the issue of institutional interplay. Interplay among regimes can cause mutual interference or foster synergy. Adopting a pragmatic stance that assumes no fundamental changes in international society, this essay suggests ways to: (1) adapt global regimes dealing with ozone depletion, climate change and biodiversity to the conditions prevailing in the polar regions; and (2) ensure that concerns arising in the polar regions receive serious consideration in global forums. Specific suggestions range from modest initiatives involving monitoring and assessment to more ambitious initiatives, such as the establishment of a chamber of regions in global regimes.
Keywords: Antarktis; biodiversitet; internasjonal samarbeid; klimaendringer; klimapolitikk; ozonlaget; polarområdene

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Establishing chronologies from acid-insoluble organic 14C dates on Antarctic (Ross Sea) and Arctic (North Atlantic) marine sediments - Licht, Kathy J; Cunningham, Wendy L; Andrews, John T; Domack, Eugene W; Jennings, Anne E (Polar Research, 1998)
Keywords: Rosshavet; Sørishavet; paleoseanografi; polarområdene; sedimentologi

A Comparison of the CCM3 Model Climate Using Diagnosed and Predicted Condensate Parameterizations - Rasch, Philip J.; Kristjánsson, Jón Egill (Journal of Climate, 1998)
A parameterization is introduced for the prediction of cloud water in the National Center for Atmospheric Research Community Climate Model version 3 (CCM3). The new parameterization makes a much closer connection between the meteorological processes that determine condensate formation and the condensate amount. The parameterization removes some constraints from the simulation by allowing a substantially wider range of variation in condensate amount than in the standard CCM3 and tying the condensate amount to local physical processes. The parameterization also allows cloud drops to form prior to the onset of grid-box saturation and can require a significant length of time to convert condensate to a precipitable form, or to remove the condensate. The free parameters of the scheme were adjusted to provide reasonable agreement with top of atmosphere and surface fluxes of energy. The parameterization was evaluated by a comparison with satellite and in situ measures of liquid and ice cloud amounts. The effect of the parameterization on the model simulation was then examined by comparing long model simulations to a similar run with the standard CCM and through comparison with climatologies based upon meteorological observations. Global ice and liquid water burdens are higher in the revised model than in the control simulation, with an accompanying increase in height of the center of mass of cloud water. Zonal averages of cloud water contents were 20%–50% lower near the surface and much higher above. The range of variation of cloud water contents is much broader in the new parameterization but was still not as large as measurements suggest. Differences in the simulation were generally small. The largest significant changes found to the simulation were seen in polar regions (winter in the Arctic and all seasons in the Antarctic). The new parameterization significantly changes the Northern Hemisphere winter distribution of cloud water and improves the simulation of temperature and cloud amount there. Small changes were introduced in the cloud fraction to improve consistency of the meteorological parameterizations and to attempt to alleviate problems in the model (in particular, in the marine stratocumulus regime). The small changes did not make any appreciable improvement to the model simulation. The new parameterization adds significantly to the flexibility in the model and the scope of problems that can be addressed. Such a scheme is needed for a reasonable treatment of scavenging of atmospheric trace constituents, and cloud aqueous or surface chemistry. The addition of a more realistic condensate parameterization provides opportunities for a closer connection between radiative properties of the clouds, and their formation and dissipation. These processes must be treated for many problems of interest today (e.g., anthropogenic aerosol–climate interactions).
Keywords: Antarktis; klimamodeller; klimatologi; meteorologi; polarområdene

The effects of personality and interpersonal relations on crew performance during space simulation studies - Sandal, Gro Mjeldheim (Life Support & Biosphere Science, 1998)
There has been a substantial increase in the number of people living and operating in isolated, confined, and artificially engineered environments, such as spacecraft, deep diving, weather stations, submarines, and polar outposts. This article gives an overview of research undertaken in a variety of extreme environments in an effort to better understand how semiautonomous, task-oriented groups operating within these environments develop over time, as well as identification of the individual characteristics that promote performance under such circumstances. Research reviewed includes space simulation studies for the European Space Agency (ESA) where groups were isolated in hyperbaric chambers, as well as findings from polar expeditions, space missions, submarine missions, and other military settings. Findings from the space simulation studies in hyperbaric chambers provided empirical evidence for interpersonal issues anecdotally reported in Antarctica and in other isolated, operational team environments, such as "scapegoating" of deviant crew members, displacement of aggression to outside personnel, and time patterns in psychological reactions. No indications of a "psychological limit" for how long people can tolerate remaining in isolation and confinement were found. Certain personality characteristics were consistently associated with coping, and individuals characterized by strong achievement motivation combined with interpersonal sensitivity seemed to adapt better than others. Together, these results have implications for selection and training of people operating within extreme environments.
Keywords: Antarktis; polarekspedisjoner; polarforskere; polarområdene; psykologi

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - Van Roozendael, Michel; Peeters, P.; Roscoe, H. K.; De Backer, H.; Jones, A. E.; Bartlett, L.; Vaughan, G.; Goutail, Florence; Pommereau, Jean-Pierre; Kyro, E.; Wahlstrom, C.; Braathen, Geir; et al. (Journal of Atmospheric Chemistry, 1998)
Comparisons of total column ozone measurements from Dobson, Brewer and SAOZ instruments are presented for the period 1990 to 1995 at seven stations covering the mid- and the high northern latitudes, as well as the Antarctic region. The main purpose of these comparisons is to assess, by reference to the well established Dobson network, the accuracy of the zenith-sky visible spectroscopy for the measurement of total ozone. The strengths and present limitations of this latter technique are investigated. As a general result, the different instruments are found to agree within a few percent at all stations, the best agreement being obtained at mid-latitudes. On average, for the mid-latitudes, SAOZ O3 measurements are approximately 2% higher than Dobson ones, with a scatter of about 5%. At higher latitudes, both scatter and systematic deviation tend to increase. In all cases, the relative differences between SAOZ and Dobson or Brewer column ozone are characterised by a significant seasonal signal, the amplitude of which increases from about 2.5% at mid-latitude to a maximum of 7.5% at Faraday, Antarctica. Although it introduces a significant contribution to the seasonality at high latitude, the temperature sensitivity of the O3 absorption coefficients of the Dobson and Brewer instruments is shown to be too small to account for the observed SAOZ/Dobson differences. Except for Faraday, these differences can however be largely reduced if SAOZ AMFs are calculated with realistic climatological profiles of ozone, pressure and temperature. Other sources of uncertainties that might affect the comparison are investigated. Evidence is found that the differences in the air masses sampled by the SAOZ and the other instruments contribute significantly to the scatter, and the impact of the tropospheric clouds on SAOZ measurements is displayed.
Keywords: Antarktis; klimatologi; ozon; polarområdene; spektrofotometri; stratosfæren

Experimental formation of sea ice: importance of water circulation and wave action for incorporation of phytoplankton and bacteria - Weissenberger, Jürgen; Grossmann, Sönnke (Polar Biology, 1998)
The efficiency of physical concentration mechanisms for enrichment of algae and bacteria in newly formed sea-ice was investigated under defined conditions in the laboratory. Sea-ice formation was simulated in a 3,000 l tank under different patterns of water movement. When ice formed in an artificially generated current pattern, algal cells were substantially enriched within the ice matrix. Enrichment factors for chlorophyll a calculated from the ratio between the concentrations in ice and underlying water reached values of up to 53. Repeated mixing of ice crystals into the water column, as well as flow of water through the new ice layer, contributed to the enrichment of algae in the ice. Wave action during ice formation revealed lower phytoplankton enrichment factors of up to 9. Mixing of floating ice crystals with underlying water and pumping of water into the ice matrix by periodical expansion and compression of the slush ice layer were responsible for the wave-induced enrichment of algal cells. Physical enrichment of bacteria within the ice was negligible. Bacterial biomass within new ice was enhanced only when the concentration of algae was high. At low algal biomass, bacteria experienced substantial losses in the ice, most likely due to brine drainage, which were not observed for the microalgae. Bacterial cells are therefore not scavenged by ice crystals and the observed enrichment and sustainment of bacterial biomass within newly formed ice depend on their attachment to cells or aggregates of algae. Division rates of bacteria changed only slightly during ice formation.
Keywords: Sørishavet; Weddellhavet; alger; bakterier; fytoplankton; havis; marin biologi; polarområdene

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Analysis of merged SMMR-SSMI time series of Arctic and Antarctic sea ice parameters 1978–1995 - Bjørgo, Einar; Johannessen, Ola M.; Miles, Martin W. (Geophysical Research Letters, 1997)
The most consistent means of investigating the global sea ice cover is by satellite passive microwave sensors, as these are independent of illumination and cloud cover. The Nimbus 7 Scanning Multichannel Microwave Radiometer (SMMR) and the Defense Meteorological Satellite Program (DMSP) Special Sensor Microwave Imager (SSMI) provide information on the global sea ice cover from 1978 to present. The two instruments flew simultaneously during a 6-week overlap period in July and August 1987, thus enabling intercomparison of the two sensors. Brightness temperatures are corrected for instrument drift and calibration differences in order to produce continuous time series of monthly averaged Arctic and Antarctic sea ice extent and sea ice area through the use of the NOrwegian Remote Sensing EXperiment (NORSEX) algorithm, which relates brightness temperatures to ice concentration. Statistical analysis on the time series estimates the decreases in Arctic ice extent and ice area to be 4.5% and 5.7%, respectively, during the 16.8-year observation period. The overall trends established here serve to better define and strengthen earlier assertions of a reduced ice cover, based on analysis of SMMR and SSMI data taken separately. These results are consistent with GCM simulations that suggest retreat of the sea ice cover under global warming scenarios.
Keywords: Antarktis; global oppvarming; havis; klimaendringer; meteorologi; polarområdene; satellite mikrobølgesensorer

Cold resistance and metabolic activity of lichens below 0°C - Kappen, Ludger; Schroeter, Burkhard; Scheidegger, Christoph; Sommerkorn, Martin; Hestmark, Geir (Proceedings of the F3.1, F3.4, F2.4 and F3.8 Symposia of COSPAR Scientific Commission F, 1996)
Laboratory measurements show that lichens are extremely tolerant of freezing stress and of low-temperature exposure. Metabolic activity recovered quickly after severe and extended cold treatment. Experimental results demonstrate also that CO2 exchange is already active at around −20°C. The psychrophilic character of polar lichen species is demonstrated by optimum temperatures for net photosynthesis between 0 and 15°C. In situ measurements show that lichens begin photosynthesizing below 0°C if the dry thalli receive fresh snow. The lowest temperature measured in active lichens was −17°C at a continental Antarctic site. The fine structure and the hydration state of photobiont and mycobiont cells were studied by low-temperature scanning electron microscopy (LTSEM) of frozen hydrated specimens. Water potentials of the frozen system are in the range of or even higher than those allowing dry lichens to start photosynthesis by water vapor uptake at +10°C. The great success of lichens in polar and high alpine regions gives evidence of their physiological adaptation to low temperatures. In general lichens are able to persist through glacial periods, but extended snow cover and glaciation are limiting factors.
Keywords: Antarktis; botanikk; frostresistens; lav; planter; polarområdene

Lack of population subdivision among the minke whales (Balaenoptera acutorostrata) from Icelandic and Norwegian waters based on mitochondrial DNA sequences - Bakke, Ingrid; Johansen, Steinar; Bakke, [Øyvind]; El-Gewely, Mohamed Raafat (Marine Biology, 1996)
The minke whale (Balaenoptera acutorostrata) is subject to commercial whaling, but stock identification and assessment are still uncertain. Mitochondrial DNA (mtDNA) sequences were determined to examine the population structure of minke whales from the central and northeastern parts of the North Atlantic, as well as the Antarctic regions IV and V. The analyses include 345 nucleotide positions of the control region of 110 individuals, and 250 nucleotide positions of the NADH dehydrogenase subunit 2 gene for a representative selection of North Atlantic minke whales. Maximum parsimony analyses and sequence divergence calculations did not reveal any genetic differentiation between individuals from the central and northeastern parts of the North Atlantic. These results do not support the International Whaling Commission's separation of minke whales in this area into different management units, and they are in conflict with previously reported results from allozyme analyses. Comparison of minke whale control region sequences showed that the sequence diversity of North Atlantic minke whales is substantially lower (0.0065) than that of Antarctic minke whales (0.0166), and clearly demonstrated that individuals from these two areas represent genetically distinct populations.
Keywords: Sørishavet; bioteknologi; genetikk; hvaler; marin biologi; polarområdene

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Effects of UV radiation on post-bloom phytoplankton populations in Kvalsund, North Norway - Walter Helbling, E.; Eilertsen, Hans Chr.; Villafañe, Virginia E.; Holm-Hansen, Osmund (Journal of Photochemistry and Photobiology B: Biology, 1996)
Our studies in the coastal waters in North Norway show that rates of photosynthesis of natural phytoplankton assemblages are strongly inhibited by solar UV radiation. When exposed to high irradiances of direct solar radiation, photosynthetic rates were increased by approximately 150% when all UV radiation was excluded from samples, with UVB radiation being responsible for approximately 50% of the total inhibition. There was no discernible threshold value for inhibition of photosynthesis by UV radiation, even at UV (280–400 nm) irradiances as low as 0.1 W m−2. When natural assemblages were incubated in situ, inhibition of photosynthetic rates were detectable down to 10 m, where solar irradiance was about 3% of the radiation incident on the sea surface. Based on the inhibition of photosynthetic rates at very low fluences of UV radiation, post-bloom assemblages of phytoplankton in North Norway and possibly also in the Arctic ocean appear to be more sensitive to solar UV radiation than phytoplankton from the Southern Ocean.
Keywords: Sørishavet; fotosyntese; fytoplankton; marin biologi; polarområdene; ultrafiolett stråling

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler

Rock mapping of glaciated areas by satellite image processing - Salvini, Francesco; Della Maggiore, Roberto; Fortunati, Luciano; Mazzarini, Francesco (Polar Research, 1994)
Keywords: Antarktis; geologi; polarområdene; satellitt bilder

Ecology of sea ice biota. 1. Habitat, terminology, and methodology - Horner, Rita; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjorn; Hoshiai, Takao; Legendre, Louis; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
Polar regions are covered by extensive sea ice that is inhabited by a variety of plants and animals. The environments where the organisms live vary depending on the structure and age of the ice. Many terms have been used to describe the habitats and the organisms. We here characterize the habitats and communities and suggest some standard terms for them. We also suggest routine sampling methods and reporting units for measurements of biological and chemical variables.
Keywords: Sørishavet; biodiversitet; havis; marin biologi; polarområdene; økologi

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi

The ecophysiology of under-ice fauna - Aarset, Arne V (Polar Research, 1991)
Keywords: Antarktis; amfipoder; fauna; havis; polarområdene; sjøis; zoologi; økofysiologi

The physiology of polar marine zooplankton - Clarke, Andrew; Peck, Lloyd S (Polar Research, 1991)
Keywords: Sørishavet; marin biologi; polarområdene; zooplankton

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

Light and productivity of phytoplankton in polar marine ecosystems: a physiological view - Sakshaug, Egil; Slagstad, Dag (Polar Research, 1991)
Keywords: Sørishavet; fysiologi; fytoplankton; planteplankton; polarområdene

Sandefjord - et naturlig polarforskningssenter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Antarktis; Norsk Polarinstitutt; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L. (Polar Research, 1990)
Keywords: Antarktis; fugler; marin ornitologi; næring; polarområdene

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L (Polar Research, 1990)
Keywords: Antarktis; fugler; ornitologi; polarområdene; zoologi

Some Nitzschia and related diatom species from fast ice samples in the Arctic and Antarctic - Medlin, Linda K.; Hasle, Grethe Rytter (Polar Biology, 1990)
Some Nitzschia and closely related species have been examined in the light and electron microscopes from fast ice samples in the Arctic and Antarctic. Nitzschia neofrigida, forming arborescent colonies, and Nitzschia promare, forming loose ribbon colonies, are described as new species, both probably included in the distribution of other similar species. A new combination, Auricula compacta, represents the first report of this genus from ice samples. Colony formation is reported for the first time in Nitzschia arctica and Nitzschia taeniiformis. No biopolar species were found and several reports of Arctic species in Antarctic ice samples have been refuted.
Keywords: Antarktis; alger; biodiversitet; biologi; botanikk; diatomeer; fytoplankton; planteplankton; polarområdene

Bibliographia Phytosociologica. Norwegian possessions in the polar regions - Sunding, Per (Excerpta botanica, Sectio B, 1990)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; bibliografi; botanikk; polarområdene

A hundred years of Norwegian exploration of the polar regions - Orheim, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1989)
Keywords: Antarktis; Norge; ekspedisjoner; oppdagelsesreiser; polarområdene

Proposed terminology and reporting units for sea ice algal assemblages - Horner, Rita A; Syvertsen, Erik E; Thomas, David P; Lange, Carina (Polar Biology, 1988)
Keywords: Antarktis; alger; havis; marin biologi; polarområdene; sjøis

Aleksandr Stepanovich Kuchin: the Russian who went south with Amundsen - Barr, William (Polar Record, 1985)
Aleksandr Stepanovich Kuchin (1888–1912) was already an experienced mariner and oceanographer when Amundsen invited him to join the Fram expedition of 1910–12. Expecting a voyage through the Barents Sea, Kuchin found himself on an expedition to the Antarctic. While Amundsen's sledging parties sought the South Pole, Kuchin remained with the ship, completing an excellent oceanographic survey of the southern Atlantic Ocean. Returning to Russia in 1912 he was recruited, by the geologist and explorer V. A. Rusinov to join a scientific expedition to Svalbard. As deputy leader of the party and captain of Gerkules, the expedition ship, Kuchin played an important role in the Svalbard survey. Then once again found himself heading in an unexpected direction: on completing the Svalbard work, Rusanov decided to attempt the Northern Sea Route to the Bering Strait. Gerkules disappeared and was never seen again; her loss, presumably in the Kara Sea, brought to an untimely end the career of a promising young polar explorer.
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; biografier; oseanografi; polarområdene

Norge og den sovjetiske polarforskning i nord og sør - Magnus, Morten H (Farmand, 1983)
Keywords: Antarktis; ekspedisjoner; polarforskning; polarområdene

Amundsen's route to the South Pole - Drewry, David John; Huntford, Roland (Polar Record, 1979)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Norsk polarpolitikk ut av tåkeheimen - Leistad, Geirr I (Farmand, 1978)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene; polarpolitikk

Med Amundsen til Sudpolen. Dagbokblad - Bjaaland, Olav (Syn og segn, 1975)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; polarområdene

Antarktis i fokus - hva gjør norsk forskning? - Orheim, Olav (Forskningsnytt, 1975)
Keywords: Antarktis; NARE ekspedisjoner; geologi; glasiologi; havis; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; polarområdene

The New Development in the Polar Regions - Sollie, Finn (Cooperation and Conflict, 1974)
Due to factors connected with modern technological developments and with the increasing global demand for new sources of raw materials, there is today a growing interest in the possibilities for economic exploitation of the polar regions. This makes for a new development in these regions; a development comprising and affecting such fields as science and technology as well as economy, transportation, military strategy and ecology. The present paper discusses this new development and its implications in an international perspective. Special attention is paid to the significance - in the physical/ geographical sense and otherwise - of the polar regions in the global context. A special section deals, on a general level, with 'the problem of the new territories', and the polar regions are discussed as new territories. Pointing out the risks and dangers inherent in the present and emerging developments, the author emphasizes the need for action, especially international cooperation, to meet and solve such problems. Cooperation may be facilitated through regular consultations between the states concerned, as is the case under the Antarctic Treaty. For the Arctic in particular, the author suggests a distinction between three basic zones (viz. the 'Central' the 'Intermediate' and the 'National' Arctic) as a possible point of departure for future discussion of measures of international cooperation.
Keywords: Antarktis; internasjonal politikk; polarområdene

Svalbard, Jan Mayen, antarktische Besitzungen - Gjelsvik, Tore (1969)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Sætrykk
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

Arktis og Antarktis : aktuelle problemstillinger - Sollie, Finn (Internasjonal politikk, 1968)
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

In Amundsen's Tracks on the Axel Heiberg Glacier - Herbert, Walter William (The Geographical Journal, 1963)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Some recent work on polar navigation - Foster, L R R (The Journal of The Institute of Navigation, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; navigasjon; polarområdene

Flyplasser på snø og is - Pedersen, Gunnar S. (Teknisk ukeblad : Norges fremste på teknologi, 1948)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY) 1957/1958; ekspedisjoner; logistikk; polarområdene

Vår ishavsflåte og selfangsten : ishavsskutenes innsats i arktisk og antarktisk forskning - Hansen, Rolf (Vår Flåte, 1944)
Keywords: Sørishavet; ekspedisjoner; forskning; polarområdene; selfangst

Norges livsrom - Hoel, Adolf (Det nye Norge, 1944)
Keywords: Antarktis; hvalfangst; internasjonal politikk; polarområdene; økonomi

Det Norske Geografiske Selskap (The Geographical Journal, 1939)
Keywords: Antarktis; Det Norske Geografiske Selskap; ekspedisjoner; geografi; polarområdene

Det nye norske land i Antarktis - Isachsen, Fridtjov (Mellanfolkligt samarbete, 1939)
Keywords: Dronning Maud Land; Norge; geografi; hvalfangst; internasjonal politikk; polarområdene

The new Norwegian dependency in the Antarctic - Isachsen, Fridtjov (Le Nord : Revue internationale des pays du nord = International review of the northern countries, 1939)
Keywords: Dronning Maud Land; Norge; geografi; hvalfangst; internasjonal politikk; polarområdene

Sledge Dogs on Amundsen's South Polar Journey - Hanssen, Helmer (Polar Record, 1937)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; oppdagelsesreiser; polarområdene; sledehunder; sydpolen

Mot Fremtidenn - Brøgger, Anton Wilhelm (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1936)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; polarområdene; sydpolen

Carsten Borchgrevink - Hoel, Adolf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Keywords: Antarktis; Carsten Borchgrevink; ekspedisjoner; oppdagelsesreiser; polarområdene

Norwegians in the Antarctic - Aagaard, Bjarne (The American-Scandinavian Review, 1934)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Antarctic Circumnavigation by the "Norvegia" (Geographical Review, 1931)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; polarområdene

Bemerkungen zu K.Lampe: Versuch einer politischen Geographie der Polargebiete - Braastad, Johan (Geographischer Anzeiger, 1931)
Keywords: Antarktis; geografi; polarområdene; politikk

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Geografisk kronikk - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Keywords: Antarktis; ekspedisjoner; historie; polarforskning; polarområdene

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Whaling and Exploring in the Antarctic - Aagaard, Bjarne (Norwegian Trade Review, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Amundsen: Supreme Adventurer - Finley, John H (Geographical Review, 1929)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; forskning; polarområdene

The Norwegian South Polar Expedition - Amundsen, Roald (Scottish Geographical Magazine, 1913)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarområdene

The Norwegian South Polar Expedition - Amundsen, Roald (The Geographical Journal, 1913)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene

The Norwegian South Polar Expedition: Discussion - Shackleton, Ernest; Bruce, W S (The Geographical Journal, 1913)
Keywords: Antarktis; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarområdene

Amundsen`s Attainment of the South Pole (The National geographic magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen's Expedition to the South Pole (Bulletin of the American Geographical Society, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Litt om vore ski, bindinger og fotbeklaedning samt deres betydning for sydpolsfaerden - Amundsen, Roald (Foreningen Til Ski-Idrettens Fremme. Årbok, 1912)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser; polarområdene; ski; skisport; sydpolen

Amundsen`s Antarctic Explorations - Brown, R N Rudmose (Scottish Geographical Magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Plan for en polarfærd 1910-1917. Foredrag tirsdag den 10.november 1908 med efterfølgende bemerkninger af professorene Mohn og Nansen - Amundsen, Roald (Det Norske Geografiske Selskabs Aarbok, 1909)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser; polarområdene

Souveränitätsverhältnisse der Polargebiete : III. die südpolaren Gebiete - Smedal, Gustav ([Nordländer])
Keywords: Antarktis; Bouvetøya; Peter I. Øy; internasjonal; polarområdene; politikk